One-Pot Synthesis of Naphthalen-2-Thiazolidinones as Potential Breast Cancer Therapeutics: An Integrative Approach Using Network Pharmacology, Biomolecular Simulations and in Vitro Evaluation - Chilamakuru Naresh Babu; Mazin Aboobaida Abdalla Abdelaziz; N D Nizamuddin; Riyaz Ali M. Osmani; Gundawar Ravi; Gollaprolu Supriya; Chagaleti Bharath Kumar; Kesavan Bhaskar Reddy; Umme Hani; Singirisetty Triveni (Journal of Pharmaceutical Innovation, 2027)

Harnessing CRISPR-Cas technology for insect pest control: current advances and future perspectives - Naresh Kumar Arjunan; Venkatesan Thiruvengadam (Molecular Biology Reports, 2026)

Multi-level biomarker responses to potentially toxic elements (PTEs) contamination in a coastal bivalve from the Maharashtra coast, India - Shubra Singh; Diganta Dey; M. Harshavarthini; Edward Inpent Campal; Saurav Kumar; Nalini Poojary; Manoj Pandit Brahmane; Ashok Kumar Jaiswar; Naresh S. Nagpure (Marine Pollution Bulletin, 2026)

Assessment of risk factors of bovine astrovirus and diarrhea in dairy farms of Northern India - Raman Mehtani; Parveen Kumar; Sanjeevna K. Minhas; Ritu Panghal; Rajeev Kumar; Deepika Sheoran; Akhil K. Gupta; Yogesh Bangar; Rajesh Chhabra; Naresh Jindal (Preventive Veterinary Medicine, 2026)

Implementation of Electrocoagulation process for Simultaneous Removal of Antibiotic Tetracycline and Chemical Oxygen Demand from Municipal Wastewater - Amitesh; R. Naresh Kumar (Water, Air, & Soil Pollution, 2026)

Thermosetting epoxy plastics as emerging environmental contaminant: Occurrence, toxicity and sustainable mitigation strategies - Jeyaraj Jeyavani; Lakkireddy Tejasvini Reddy; Sudha Gandhinathan; Naresh Kumar Sharma (Journal of Environmental Chemical Engineering, 2026)

Movement ecology and habitat preferences of translocated greater one-horned rhinoceros in their historic range in Nepal - Rishi Ranabhat; Hari Prasad Pandey; Shravan Kumar Ghimire; Naresh Subedi; Babu Ram Lamichhane; Khim Bahadur KC; Tek Narayan Maraseni (Journal for Nature Conservation, 2026)

Modeling future hydrology in the Tungabhadra Basin: interactions between land use dynamics and climate change - Suram Anil; Aadhi Naresh; Arram Vijay Kumar Reddy (Journal of Earth System Science, 2026)

Energy and Carbon Footprints with Operational Cost Analysis of Various Paddy Straw Management Machinery in North-Western India - Swapnil Choudhary; Ganesh Upadhyay; Neeraj Kumar; Naresh Sihag; Bharat Patel; Vijaya Rani (Agricultural Research, 2026)

Origin and evolution of the Erinpura Granites, NW India: Evidence from geochemistry and SrNd isotopes - Devsamridhi Arora; Naresh Chandra Pant; Waliur Rahaman; Raghuram; Pankaj Kumar (Lithos, 2026)

Enhanced multi-well lithological correlation in eastern Indian coalfields using XGBoost and dynamic time warping - Naresh Kumar Seelam; Thinesh Kumar; G. Srinivasa Rao; D. Voleti (Journal of Applied Geophysics, 2026)

Understanding the physiology of lactose intolerance and an insight on the recent trends on management strategies - Mohamed Suneer; Pathil Thabshira; Manu Mohan; Naresh Kumar; Saleem Akhtar; P Abdul Rasheed (International Dairy Journal, 2026)

Pediatric Vulnerability to Inhaled Particulate Matter in Singrauli’s Coal Energy Belt: A Dosimetric Assessment Using the Multiple-Path Particle Dosimetry (MPPD) Model - Bhupendra Kumar; Naresh Chandra Gupta (Air Quality, Atmosphere & Health, 2026)

Underlying physiological mechanism and expression analysis of important genes associated with extended shelf-life in Cucumber (Cucumis sativus L.) - Pyla Suresh; Khushboo Kumari; Malatesha Kenchikoppa; Laxman Nandi; A. D. Munshi; G. Boopalakrishnan; S. Gopala Krishnan; Naresh Kumar Soora; T. K. Behera; S. S. Dey (Acta Physiologiae Plantarum, 2026)

Evaluating Reference Evapotranspiration ( ETo ) Calculation Methods and Quantifying Climate‐Driven Change in Irrigation Demand Across Nepal's Terai - Umesh Kumar Sujakhu; Rajesh Khatakho; Naresh Suwal; Ayush Poudel (International Journal of Climatology, 2026)
Global food security faces growing pressure from population growth and climate change. Improving water productivity requires optimizing irrigation through accurate reference evapotranspiration (ETo) estimates, yet selecting reliable ETo methods remains difficult in data‐scarce Nepal. This study evaluates ETo in the Terai region of Nepal using data from 14 meteorological stations over a historical period (1989–2014) using nine empirical and physically based methods. Coupled Model Intercomparison Project Phase 6 (CMIP6) Global Climate Models (GCMs) data for temperature and precipitation under Shared Socioeconomic Pathways (SSP) SSP245 and SSP585 scenarios were used after downscaling and bias correction to develop a multi‐model ensemble for near (2027–2051), mid (2052–2076), and far‐future (2077–2100) periods. Using these projections, ETo, crop water requirement (CWR), and irrigation water requirements (IWR) were estimated and compared with historical conditions. Among the evaluated models, the Turc (TU) model consistently outperformed the other models, confirming its robustness for ETo estimation. Climate projections indicate increased winter precipitation, particularly under the SSP585 far‐future scenario, alongside rising maximum and minimum temperatures across all scenarios, with stronger warming during winter than the monsoon season. The highest ETo occurred from April to June, and overall ETo is projected to increase under both scenarios, with a pronounced rise (40.7%) in January under SSP585, while slight monsoon‐season declines (0.2%–2.3%) are projected under SSP245. CWR peaks during July–September, with the highest values observed in July. Notable increases in CWR are projected in July under SSP585 mid‐ and far‐future scenarios and during winter across all scenarios. IWR exhibits strong seasonality, peaking in the monsoon months, with most stations showing moderate annual increases (5%–14%), although some stations experience substantial declines (13%–36%). Overall, the results highlight strong spatial heterogeneity in future irrigation demand, emphasizing the need for region‐specific, climate‐resilient water management strategies across the Terai.

Edwardsiella ictaluri infection in farmed striped catfish Pangasianodon hypophthalmus in India - Chandra Bhushan Kumar; Tamal Seth; Devarshi Ranjan; Dev Kumar Verma; Naresh Kumar Sood; Neeraj Sood; Pravata Kumar Pradhan; Joykrushna Jena (Veterinary Research Communications, 2026)

Prebreeding using untapped rice genetic resources: linking the gap between biodiversity and crop improvement - Santhosh Venna; Divya Balakrishnan; P. K. Singh; B. Arun; Suneetha Kota; S. Amurutha Rao; Naresh Kumar Sahu; S.V. SaiPrasad; R. M. Sundaram (Journal of Crop Science and Biotechnology, 2026)

Enhancing Berry Excellence: GABA-Induced Stimulation of Anthocyanin Biosynthesis and Antioxidant Defense in ‘Flame Seedless’ Grapes - Khushi Kumari; Rachna Arora; Naresh Kumar Arora; Shalini Jhanji (Applied Fruit Science, 2026)

Internet of Things- and Machine Learning-Based Soil Parameter Monitoring System for Optimal Crop Recommendation - Venkata Sudhakar Chowdam; M. Venkata Naresh; Ganjikunta Ganesh Kumar (Applied Fruit Science, 2026)

Radical Quenching and LOX Inhibiting Properties of Indole Derivatives: A Plausible Mechanism of Action Through HAT, SET-PT and SPLET Pathway - Km Srishti; Oseen Negi; Anamika Gusain; Naresh Kumar; Rahul Kumar Vishwakarma; Prasanta Kumar Hota (Journal of Fluorescence, 2026)

Correction: Undrained Vertical Uplift Capacity of Bucket Foundations in Overconsolidated Clay under Two Way Cyclic Loading - Naresh Kumar Singam; Santiram Chatterjee (Geotechnical and Geological Engineering, 2026)

Isolation of bacterial extracellular vesicles from raw samples using a portable microstructured electrochemical device - Valeria Mantella; Siiri Bienz; Finn Brigger; Edouard Baulier; Marie Ramus; Nicole Zoratto; Steffen Honrath; Kumar Naresh; Sibilla Sander; Jörn Dengjel; Renato Zenobi; Vadim Krivitsky; et al. (Drug Delivery and Translational Research, 2026)
Bacterial extracellular vesicles (EVs) are nanosized vesicles released by both Gram-negative and Gram-positive bacteria, playing critical roles in microbial communication, host-pathogen interactions, and immune modulation. Despite their significance in research and clinical applications, conventional isolation methods, such as ultracentrifugation (UC), are often slow, labor-intensive, and susceptible to contamination. In this study, we evaluated a novel portable microstructured electrochemical device (PMED) designed for rapid and selective bacterial EV isolation directly from biological samples. Using immunoaffinity-based capture and voltage-triggered release, the device-isolated EVs from Gram-negative Escherichia coli ( E. coli ), Gram-positive Lactobacillus fermentum ( Lb. fermentum ) culture supernatants and from urine samples spiked with E. coli , showing superior purity compared to UC. Characterization through nanoparticle tracking analysis (NTA), dynamic light scattering (DLS), and Western blot confirms enhanced selectivity and reduced contaminants. Functional assays demonstrated that device-isolated Lb. fermentum EVs selectively activated Toll-like receptor 4 (TLR4) without triggering TLR2, unlike UC-isolated EVs, suggesting a more refined immunomodulatory effect. These findings highlight the device’s translational potential for EV-based diagnostics, particularly for noninvasive urinary tract infection detection, and its broader applications in studying bacterial communication and immune regulation. Graphical abstract

Addressing the escalating threat of antimicrobial resistance (AMR) in fisheries and aquaculture - Mutum Deepti; Nitesh Kumar Yadav; Naresh Raj Keer; Dushyant Mahavadiya; Parvind Kumar; Madhulika; Dharmendra Kumar Meena (Aquaculture International, 2026)

Evaluating PM2.5 acidity using thermodynamic models and source contributions in Eastern India - Abisheg Dhandapani; Jawed Iqbal; Radhakrishnan Naresh Kumar; Delwin Pullokaran; Diksha Haswani; Deeksha Shukla; Ramya Sunder Raman (Environmental Monitoring and Assessment, 2026)

Evaluation of MERRA-2 PM2.5 species at three locations in India and their historical (1999–2019) trends - Sandeep Devaliya; Sayak Patra; Prem Maheshwarkar; Ankur Bhardwaj; Diksha Haswani; Deeksha Shukla; Ramya Sunder Raman; Abisheg Dhandapani; R. Naresh Kumar; Jithin K. P.; Lokesh Kaggere (Environmental Monitoring and Assessment, 2026)

Interleukin- 17A as an Immunomodulatory Cytokine in Animal Health and Diseases: A Systematic Review - Anita Dalal; Gajendra Singh; Akhil K. Gupta; Naresh Kumar Kakker; Sonu Kumari (Veterinary Immunology and Immunopathology, 2026)

A ∼1.6 Ga accretionary event in the polymetamorphic Lesser Himalaya, India: Insights into late-stage assembly of the Columbia supercontinent - Mallickarjun Joshi; Biraja P. Das; Shubham Patel; Daniel Pastor-Galán; Naresh C. Pant; A. Krishnakanta Singh; Govind Oinam; Alok Kumar; Ankit Kumar (Precambrian Research, 2026)

Unveiling the Photocatalytic and Antimicrobial Activities of Bio-waste inspired ZnO Nanoparticles - Parmeshwar Lal Meena; Ajay Kumar Surela; Lata Kumari Chhachhia; Naresh Kumar Nirmal (Water, Air, & Soil Pollution, 2026)

Remote Sensing-Based Leaf Area Index Estimation of Spring Wheat Through Machine-Learning Approaches - Pratibha Prakash; Swadhina Koley; Soora Naresh Kumar; Ramesh Chand Harit; Jitendra Kumar Gupta; Ravi Kumar (Journal of the Indian Society of Remote Sensing, 2026)

Tomographic image of shear wave structure of NE India based on analysis of love wave data - Nongmaithem Menaka Chanu; Naresh Kumar; Sagarika Mukhopadhyay; Sanjay K. Verma; Shantanu Pandey (Journal of Seismology, 2026)

Estimation of Non-exhaust Particulate Matter Emissions from Road Transportation in Indian States - Sandhiya Lakshmanan; Anupama Upadhayay; Naresh Kumar; Shivnarayan Nishad (International Journal of Environmental Research, 2026)

Integrating statistical analysis and decision-making to assess flood susceptibility in Indian mountainous agroecosystems - Swadhina Koley; Manjar Alam; Soora Naresh Kumar (Journal of Earth System Science, 2026)

Remote sensing and machine learning approaches for heat island mapping and analysis: a review and framework for sustainable smart cities - Venkata Sudhakar Chowdam; Venkata Naresh M; Ganjikunta Ganesh Kumar; Suresh Babu Potladurty (Environment, Development and Sustainability, 2026)

Retraction Note: Income, coal consumption, and the environmental Kuznets curve in Vietnam - Nhan Dang Tran; Naresh Chandra Sahu; Pushp Kumar (Environmental Science and Pollution Research, 2026)

Estimation of consolidated undrained bearing capacities of tripod bucket foundations in clay - Naresh Kumar Singam; Santiram Chatterjee (Marine Georesources & Geotechnology, 2026)

Nano-antimicrobial peptides (Nano-AMPs) to combat resistant gram-negative bacteria - Naveed Saleem; Naresh Kumar; Emad El-Omar; Mark Willcox; Xiao-Tao Jiang (Drug Delivery and Translational Research, 2026)
The emergence of antimicrobial resistance (AMR) poses a critical threat to public health worldwide, making conventional antibiotics ineffective against multidrug-resistant (MDR) pathogens. This literature review examines the potential therapeutic applications of nano-antimicrobial peptides (Nano-AMPs), with a focus on multidrug-resistant pathogens prioritized by the World Health Organisation (WHO). Antimicrobial peptides (AMPs) are essential components of the innate immune system with broad-spectrum bactericidal and immunomodulatory properties, and have emerged as promising alternatives to conventional antibiotics because of their unique mechanisms of action (e.g., membrane disruption, pore formation, and immunomodulation). Currently, the clinical translation of AMPs is hindered by several challenges, including enzymatic and non-enzymatic degradation, poor bioavailability, and biocompatibility issues, as well as local and systemic adverse events. To address these concerns, recent advancements in nanocarrier delivery systems offer novel solutions, enabling selected and targeted drug delivery, enhanced bioavailability, and controlled and sustained AMP release. Lipid-based nanocarriers (e.g., liposomes), polymeric and other nanocarrier systems improve peptide solubility and limit off-target events, while inorganic carriers like gold, silver, and silica nanoparticles facilitate functionalization and synergism to combat MDR Gram-negative infections. Despite promising findings, challenges such as production, long-term efficacy and safety, and regulatory approval persist. Therefore, interdisciplinary efforts, such as advanced machine learning methods alongside conventional pharmacological approaches, may be needed to optimize nanocarrier designs and validate clinical efficacy and safety in preclinical and clinical trials. This review critically analyses the latest evidence on different nanocarriers and their synergistic effects, highlighting their transformative potential to combat AMR, thereby offering insights to develop next-generation antibiotics, particularly against Gram-negative pathogens.

Can agroforestry–conservation agriculture integration improve soil organic matter (SOM) quality? An FTIR–spectroscopic investigation - Bharti; Sovan Debnath; Asha Ram; Avijit Ghosh; Susheel Kumar Singh; Bijoy Chanda; Naresh Kumar; Inder Dev; Tufleuddin Biswas; Sushil Kumar; Amit Kumar Singh; Badre Alam; et al. (Soil and Tillage Research, 2026)

Hyperparameter optimized feature selected machine-learning models for groundwater quality index – A post-monsoon case study in Jajpur, Odisha, India - Sushree Sabinaya; Nageswar Sahu; Biswanath Mahanty; Naresh Kumar Sahoo; Sunil Kumar Sahoo; Vivekanand Jha (Journal of Water Process Engineering, 2026)

Converting brewery wastewater into Bioenergy: Anaerobic digestion performance and digestate suitability by ecotoxicological assessment - Mariana Pires Maria; Nádia Hortense Torres; Victor Ruan Silva Nascimento; Halana Santos Lisboa; Carlos André Oliveira Santos; Lucas Azevedo; Ajay Kumar; Ram Naresh Bharagava; Luiza Helena da Silva Megale; Jonathas Eduardo Miranda Gomes; Ranyere Lucena Souza; Eliane Bezerra Cavalcanti; et al. (Biomass and Bioenergy, 2026)

Molecular insights into astrovirus, kobuvirus and rotavirus a coinfection in pigs (Sus domesticus) from Haryana, India - Ritu Panghal; Parveen Kumar; Sanjeevna K. Minhas; Rekha Yadav; Raman Mehtani; Deepika Sheoran; Sweety Kalonia; Akhil Kumar Gupta; Mahavir Singh; Rajesh Chhabra; Anupama Dahiya; Naresh Jindal (Tropical Animal Health and Production, 2026)

Undrained Vertical Uplift Capacity of Bucket Foundations in Overconsolidated Clay under Two Way Cyclic Loading - Naresh Kumar Singam; Santiram Chatterjee (Geotechnical and Geological Engineering, 2026)

Nitrate sensor: characterizing the role of putative nitrate transporter1 (NRT 1) gene in augmenting the plasticity of wheat root and yield under $${\text{eCO}}_{2}$$ and terminal heat - Abhishek Chitranashi; G. A. Nandini; Mallesh Gampa; Ashok Kumar; Suneha Goswami; Vinutha T.; Neelu Jain; Bhupinder Singh; Gyan P. Mishra; Soora Naresh Kumar; Girish Jha; Viswanathan C.; et al. (Cereal Research Communications, 2026)

Porcine astrovirus: a review - Parveen Kumar; Ritu Panghal; Sanjeevna K. Minhas; Rekha Yadav; Raman Mehtani; Vijay Kumar; Anshul Lather; Sunil Raj; Mohd Yaqoob Wani; Jobin Jose Kattoor; Mahavir Singh; Rajesh Chhabra; et al. (Archives of Virology, 2026)

Corrigendum to “Delineation of crustal structure and composition in the Northwest Himalaya and adjoining Indo-Gangetic Plain” [Tectonophysics 904 (2025) 230717] - Amlanjyoti Das; Devajit Hazarika; Pritom Neog; Naresh Kumar; Dilip Kumar Yadav (Tectonophysics, 2026)

Structure-driven selective detection of hydroquinone over catechol via a NiS₂–MoO₃@rGO-modified electrode: Mechanistic insights into electron transfer, adsorption dynamics, and redox discrimination - Naresh A. Rajpurohit; Kaushalya Bhakar; Kajal Panchal; Ubaid Sidiqi; Dinesh Kumar (Chemical Engineering Journal, 2026)

Potential tuneable glucose oxidation to selective C6 molecules and CC cleavage, and parallel green H2 production: Sustainable high current density electrolysis - Inderjeet Chauhan; Kshirodra Kumar Patra; Pothoppurathu M. Vijay; Naresh Nalajala; Shweta Mehta; Kavita Joshi; Sapna Ravindranathan; Chinnakonda S. Gopinath (Chemical Engineering Journal, 2026)

Insect shell chitosan nanoparticle as novel flocculants in biofloc system: An innovative resource recovery approach for sustainable aquaculture - Reshmi Debbarma; Soibam Khogen Singh; Soibam Ngasotter; Pradyut Biswas; Gusheinzed Waikhom; Nayan Chouhan; M. Bharghavi Priyadarshini; Tanmoy Gon Choudhury; Naresh Kumar Mehta (Bioresource Technology Reports, 2026)

Potential of Nanoparticles for Improving Water Quality: Recent Studies and Future Directions - Aaysha Pandey; Kamal Kishore; Shubham Sharma; Sunanda Kulshrestha; Krishna Kumar Ahirwar; Naresh Kumar Wagri; Swati Rani (Water, Air, & Soil Pollution, 2026)

Analyzing soil loss dynamics in the Indian Himalayan Region using geospatial approach - Arvind Dhaloiya; Swadhina Koley; Manjar Alam; Soora Naresh Kumar (Spatial Information Research, 2026)

Temporal Modulation of Physiological and Biochemical Mechanisms Enhances Drought Tolerance Across Developmental Stages in Field Pea (Pisum sativum L.) - Amit Sharma; Ravika Sheoran; Rajesh Yadav; Pawan Kumar; Kavita Dhaka; Deepak Kaushik; Jyoti Duhan; Naresh (Journal of Plant Growth Regulation, 2026)

Effect of pusa decomposer-mediated rice residue management on phosphorus fractionation in aggregate size classes under a rice–wheat system - Chinthala Mounika; Ranjan Bhattacharyya; T.K. Das; Livleen Shukla; Shrila Das; D.R. Biswas; B.B. Basak; Peram Nagaseshi Reddy; Sumitra Kumawat; Avijit Ghosh; Soora Naresh Kumar (Agriculture, Ecosystems & Environment, 2026)

Assessing the Effect of Substitution of Arginine with Homoarginine in Two Antimicrobial Peptides - George Nkrumah Enninful; Rajesh Kuppusamy; Elvis Tiburu; Naresh Kumar; Mark D. P. Willcox (International Journal of Peptide Research and Therapeutics, 2026)
Purpose Antimicrobial peptides show promise as broad-spectrum agents and are less likely to induce rapid resistance. However, protease sensitivity limits their potential as antibiotic alternatives. Non-canonical amino acid incorporation may enhance stability but could impact other properties. Methods The activities of four peptides (oligoarginine (PLR10), oligohomoarginine (PLHR10), Mel4, and Mel4HArg) were tested against strains of S. aureus , P. aeruginosa and E. coli. Circular dichroism (CD) was used to determine their secondary structure. Their MICs against E. coli and P. aeruginosa were re-examined after protease treatment. Cytotoxicities against L929 cell line were determined. Results MICs for the four AMPs ranged from 31.25 to > 500 µM. Total substitution of arginine with homoarginine had minimal effect on MICs of PLR10, but increased the MICs of Mel4, e.g., against S. aureus ATCC 6538 from 31.25 to > 250 µM. In 30 mM SDS, substitution with homoarginine resulted in the loss of α-helical structures. Trypsin reduced PLR10 activity against E. coli and P. aeruginosa but had less effect on PLHR10. At 62.5 µM, PLR10 reduced E. coli growth by 20% compared to 90% for PLHR10. At 125 µM, PLR10 reduced P. aeruginosa growth by 22% compared to 70% for PLHR10. Mel4HArg retained activity against E. coli post-trypsin treatment but not against P. aeruginosa . The IC 50 for PLR10 and PLHR10 (15.625 µM) against L929 cell line was below their MIC (31.25 µM), indicating low therapeutic potential. In contrast, Mel4 and Mel4HArg had IC50 > 500 µM, exceeding Mel4’s MIC for S. aureus (31.25–62.5 µM) and E. coli (125 µM), though not for Mel4HArg’s MIC against P. aeruginosa . Conclusion The total arginine substitution with homoarginine in Mel4 and PLR10 resulted in improved stability but reduced activity in Mel4 and no improvement in cytotoxicity of PLR10, highlighting the need to find balance in optimizing AMP properties.

Enhanced tannery wastewater remediation using a synergistic Bacillus licheniformis and Auxenochlorella pyrenoidosa consortium - Anuradha Devi; Devendra Kumar Patel; Gubbala Naga Venkata Satyanarayana; Vartika Jain; Ganesh Dattatraya Saratale; Luiz Fernando R. Ferreira; Ram Naresh Bharagava (Environmental Sustainability, 2026)

Uncovering a new subclade of Bacillus anthracis in India: Genomic and phylogenetic insights from recent animal isolates - Subalakshmi Kaarmegam Pandiarajan; Raison Joseph; Rani Prameela; Shivaraj Murag; Niranjana Sahoo; Lahari Laddika; Vijayalakshmi Siddavatam; Girisha Budiredla; V. Manohar Raju; Kavya Shetty; Keerthana Ranganath; Bhavana Ramakrishnaiah; et al. (Science of The Total Environment, 2026)

A novel two-stage enzyme substrate assay for rapid screening and detection of Listeria monocytogenes in milk and dairy products - Shabanam Kouser; Shreya Talan; Mandeep Balhara; Prashant Goel; Naresh Kumar; H.V. Raghu (International Dairy Journal, 2026)

Advancing air quality prediction with hyperparameter optimization and innovative feature analysis using deep learning models in Phoenix, Arizona, USA - Vijendra Kumar; Akshat Agrawal; Naresh Kedam; Saleh Alsulamy; Aditya Singh (Theoretical and Applied Climatology, 2026)

Microalgae-based treatment for wastewater management and valorization - Shailja Pant; Mukesh Goel; Naresh Kumar Sahoo; Qiuyan Yuan; Prangya Ranjan Rout (Current Opinion in Environmental Science & Health, 2025)

A Critical Review on Abatement of VOCs By Adsorption: Adsorbent Types and Their Characteristics - Kaushal Naresh Gupta; Rahul Kumar; Amit Kumar Thakur (Water, Air, & Soil Pollution, 2025)

Deciphering physiological traits response under variable sowing times and locations for grain yield consolidation in wheat (Triticum aestivum L.) - Shiv Kumar Singh; Rajbir Yadav; Manjeet Kumar; Naresh Kumar Bainsla; Kiran Gaikwad; Parsanth Babu; Sudhir Kumar; Monika Dalal; Rihan Ansari; Nasreen Saifi; Tapas Ranjan Das (Plant Physiology Reports, 2025)

Nitrate flare in root – shielding the stress effect by shaping the root system architecture and triggering the antioxidant defense network in wheat under heat - Ranjeet R. Kumar; Suneha Goswami; Vinutha Thimmegowda; Rakesh Pandey; Sudhir Kumar; Monika Dalal; Bhupinder Singh; Soora Naresh Kumar; Girish K. Jha; Gyan P. Mishra; Viswanathan Chinnusamy (Plant and Soil, 2025)

Amelioration of Arsenic Toxicity Using Phytoconstituents: Experimental Evidence, Mechanisms, and Strategies - Pothuraju Naresh; P. Harish Kumar; V. Yaswanth Naik; Deepjyoti Das; M. Mahindran; Vipan K. Parihar; V. Ravichandiran; P. Ramalingam (Reviews of Environmental Contamination and Toxicology, 2025)

Soil organic carbon stabilization inside microaggregates within macroaggregates is the major mechanism of carbon sequestration under a long-term agroforestry system in the foot hills of the Indian Himalayas - Swarnashree Barman; Ranjan Bhattacharyya; Charan Singh; A.C. Rathore; Vibha Singhal; M. Muruganandan; Anshuman Patel; Anshuman Das; S.L. Jat; P. Jha; Avijit Ghosh; D.R. Biswas; et al. (Soil and Tillage Research, 2025)

Understanding the impact of climate change on future climate extremes in the Gandak River Basin: A multi-model ensemble-based analysis - Arushi Jha; Naresh Chandra Gupta; Joshal Kumar Bansal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

New length-biased weighted inverse Rayleigh distribution, its properties, applications and stochastic comparison - Surinder Kumar; Shivendra Pratap Singh; Naresh Chandra Kabdwal (Stochastic Environmental Research and Risk Assessment, 2025)

In situ evaluation of genotoxicity and cytotoxicity associated with microplastics in an intertidal clam, Gafrarium divaricatum (Gmelin, 1791) - M. Harshavarthini; Shubra Singh; Prem Kumar; Martin Xavier; Saurav Kumar; Nalini Poojary; Madhuri S. Pathak; Kiran D. Rasal; Gajanan S. Ghode; Naresh S. Nagpure (Marine Pollution Bulletin, 2025)

Strategic morphological engineering of NiP2O6 via g-C3N4 integration for boosted electrocatalytic activity through a synergistic approach toward advanced energy conversion applications - Bodicherla Naresh; T.V.M. Sreekanth; Chandra Reddy Neeragatti Suma; Kummara Sunil Kumar; Kisoo Yoo; Jonghoon Kim (Journal of Environmental Chemical Engineering, 2025)

Development and evaluation of PANI-PecPaper strip sensor for detection of total plate count in milk and milk products - Shreya Saha; Mohit Singh; Maharshi Prajapathi; Rashmi Hogarehalli Mallappa; Naresh Kumar; Rajan Sharma; Anjali M. K; Raghu Hirikyathanahalli Vishweswaraiah (Food Control, 2025)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

Deciphering the potential Zea nicaraguensis for addressing yield plateau in maize - Priya Garkoti; Velmurugan Senthilkumar; Thotla Naresh; Sachin Prakash; T. V. Anirudh; Mayank Tiwari; Kamlesh Kumar; Narendra Kumar Singh (Genetic Resources and Crop Evolution, 2025)

Comparative Study on Morphological and Physiological Changes During Fruit Development in Three Guava (Psidium guajava L.) Cultivars - Kuldeep Kamboj; Gagandeep Kaur; Kirandeep Kaur Kang; Naresh Kumar Arora; Jaswinder Singh Brar (Applied Fruit Science, 2025)

Microbial enriched vermicompost efficiently substitutes soil nutrients, microbial populations and enzymatic activity for the growth and yield of tuberose (Agave amica Medik.) cv. Single - Mukesh Kumar; Veena Chaudhary; Vidisha Chaudhary; Ravi Kumar; Krishna Kaushik; Rajan Bhatt; R. K. Naresh; Ahmed Gaber; Akbar Hossain (Folia Microbiologica, 2025)

Response of Barrier Islands During Sea-Level Rise: Perspective from More than Fifty Years of Research - Naresh Kumar (Coastal Management, 2025)

Soil Carbon and Nutrient Cycling Regulated by Fine Roots Distribution and Dynamics in Teak (Tectona grandis L.)-Based Agroforestry System in Semi-Arid Central India - Asha Ram; Shubham Choure; Inder Dev; Naresh Kumar; Deepak Singh; Dhiraj Kumar; Sovan Debnath; S. Suresh Ramanan; Ashutosh Dwivedi; Raju Kumar; Sanjana Maurya; Subhash Babu; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Geotourism Potential of the Nakora Ring Complex, Western Rajasthan, India - Naresh Kumar; Baru Ram; Ankush Sagwal; Swati Rana (Geoheritage, 2025)

Leveraging center endosperm pigmentation for haploid seed selection in maize - Velmurugan Senthilkumar; Priya Garkoti; Shankarappa Varalakshmi; Thotla Naresh; Narendra Kumar Singh (Cereal Research Communications, 2025)

Phylogenomic analysis of bovine astrovirus expands the known repertoire of mamastrovirus genotypes in northern India - Raman Mehtani; Parveen Kumar; Sanjeevna K. Minhas; Ritu Panghal; Anshul Lather; Rajeev Kumar; Puneet Singh; Deepika Sheoran; Akhil K. Gupta; Rajesh Chhabra; Naresh Jindal (Archives of Virology, 2025)

Widespread occurrence of Tilapia parvovirus in farmed Nile tilapia Oreochromis niloticus from India - Kooloth Valappil Rajendran; Neeraj Sood; B. Madhusudhana Rao; Anisha Valsalam; Megha K. Bedekar; Kezhedath Jeena; Pravata Kumar Pradhan; Anutosh Paria; Thangaraj Raja Swaminathan; Dev Kumar Verma; Naresh Kumar Sood (Journal of Fish Diseases, 2025)
Tilapia parvovirus (TiPV) has been associated with heavy mortalities in tilapia as a single infection or in co‐infection with Tilapia lake virus (TiLV). In this study, TiPV was detected in farmed Nile tilapia, Oreochromis niloticus , from two geographical regions of India, Maharashtra and Uttar Pradesh. TiPV‐specific polymerase chain reaction (PCR) reported earlier was used in the screening. Tilapia collected from Maharashtra showed characteristic clinical signs, and TiPV was detected along with TiLV and/or Aeromonas spp. However, fish from Uttar Pradesh were apparently healthy and only TiPV could be detected in these samples. A high prevalence of TiPV was recorded from both the geographical locations, Maharashtra and Uttar Pradesh (59.6% and 95.0% respectively). The virus could be detected in tissues such as the spleen, liver, kidney, brain and mucus. The spleen appeared to be the best tissue for detecting TiPV in apparently healthy tilapia. The presence of TiPV was further confirmed through sequencing the PCR products, isolation of the virus in the cell line and electron microscopy. Sequences of the NS1 gene of the two TiPV isolates showed similarity to the earlier reported TiPV isolates. The virus could be successfully propagated in O. niloticus Liver (OnL) cell line, and cytopathic effect was observed as early as 3 days post‐infection. Furthermore, the presence of non‐enveloped icosahedral to round virus particles measuring about 26–35 nm could be demonstrated in the cytoplasm and nucleus of infected OnL cells in transmission electron microscopy. With this confirmation of the presence of the virus, India is the third country to report TiPV after China and Thailand. The detection of TiPV in co‐infection cases with TiLV and in apparently healthy Nile tilapia suggests its wide distribution and potential synergistic effect in co‐infection cases. Therefore, this emerging virus needs holistic attention to understand its virulence, host‐specificity and epidemiological risk factors.

Recent progress in the development of HSP90 inhibitors: structure–activity relationship and biological evaluation studies - Ankush Kumar; Aman Rai; Naresh Kumar Rangra; Thakur Gurjeet Singh; Samson Chibuzo Ugwuagbo; Rohit Bhatia (Molecular Diversity, 2025)

Fast degradation of chlorinated volatile organic compounds using soluble cobalt complexes - Maryam Mirabediny; Tsz Tin Yu; Jun Sun; Matthew Lee; Denis M O’Carroll; Michael J. Manefield; Biswanath Das; Naresh Kumar (Process Safety and Environmental Protection, 2025)

Enhancement of 3-hydroxyvalerate fraction in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) produced by Haloferax mediterranei fed with food waste pretreated via arrested anaerobic digestion integrated with microbial electrolysis cells - Xueyao Zhang; Naresh Kumar Amradi; Martin Moore; Amro Hassanein; Rebecca L. Mickol; Emily L. McCoy; Brian J. Eddie; Jamia S. Shepard; Jiefu Wang; Stephanie Lansing; Matthew D. Yates; Young-Teck Kim; et al. (Bioresource Technology, 2025)

Neuro-inflammation Induced by Arsenic: An Insight into Mechanisms and Pathways Involved - Annem Ravi Teja Reddy; Sakshi Ramesh Mahadik; Khushboo Choudhary; Naresh Pothuraju; Sanjiv Singh; Krishna Murti; P. Ramalingam; Nitesh Kumar (Biological Trace Element Research, 2025)

Molecular docking and molecular dynamics simulation studies of thiazole-coumarin and thiazole-triazole conjugates against Mpro and ACE2 receptor for SARS COV-2 - Deepak Mishra; Ram Singh; Nupur S. Munjal; Naresh Kumar; Prashant Kumar; Poonam; Sandeep Sharma (In Silico Pharmacology, 2025)

Insights into the biophysical and molecular mechanisms underlying enhanced growth in Brassica juncea L. under lead-induced hormesis - Shalini Dhiman; Ram Naresh; Rajesh Kumar Singh; Shiv Shanker Pandey; Renu Bhardwaj; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (South African Journal of Botany, 2025)

Plant-extract hydrogel for effective wound healing: Animal model studies - Avishek Mallick Choudhury; Subham Sekhar Mandal; Naresh Kumar Singh; Manoranjan Sahu; Pralay Maiti (Chemical Engineering Journal, 2025)

Enhancing Water Level Prediction Using Ensemble Machine Learning Models: A Comparative Analysis - Saleh Alsulamy; Vijendra Kumar; Ozgur Kisi; Naresh Kedam; Namal Rathnayake (Water Resources Management, 2025)

Thrips and mites in peppers: challenges and resistance strategies - Satyaprakash Barik; Bhabani Mahankuda; Nandini Sahu; Swapnalisha Mohapatra; V. Sridhar; Pavani Narigapalli; D. C. Lakshamanareddy; N. R. Prasannakumar; Satyapriya Singh; G. C. Acharya; Manoj Kumar Nalla; K. Madhavi Reddy; et al. (Euphytica, 2025)

History, significance and management of banded leaf and sheath blight disease of maize: a review - Lokesh Yadav; Ashwani Kumar; Naresh Kumar Yadav; Rakesh Punia; R. S. Chauhan (Cereal Research Communications, 2025)

Seismic risk potential of NW Himalaya: Inferences based on attenuation model - Vandana; Naresh Kumar (Journal of Earth System Science, 2025)

Delineation of crustal structure and composition in the Northwest Himalaya and adjoining Indo-Gangetic Plain - Amlanjyoti Das; Devajit Hazarika; Pritom Neog; Naresh Kumar; Dilip Kumar Yadav (Tectonophysics, 2025)

Integrated Approach (MCD19A2 and PM10 Datasets) for Spatiotemporal Assessment of Aerosol and Revealing Approachable Predictive Model Across the Mega-Mining Region (Jharkhand), India Along with its Accuracy Measures - Shalini Priya; Abisheg Dhandapani; Radhakrishnan Naresh Kumar; Jawed Iqbal (Journal of the Indian Society of Remote Sensing, 2025)

Cra-controlled antisense RNA-downregulation of isocitrate dehydrogenase in Escherichia coli - Jisha Elias; Vikas Sharma; G. Archana; G. Naresh Kumar (Archives of Microbiology, 2025)

Advancements in constructed wetland technology: a state-of-the-art review on bio-electrochemical processes, tidal flow dynamics, and resilience to shock loads - Rohan Kumar; Tuhin Banerji; Naresh Sharma (Environmental Science and Pollution Research, 2025)

Preferential use of organic acids over sugars by soil microbes in simulated root exudation - Julia Wiesenbauer; Stefan Gorka; Kian Jenab; Raphael Schuster; Naresh Kumar; Cornelia Rottensteiner; Alexander König; Stephan Kraemer; Erich Inselsbacher; Christina Kaiser (Soil Biology and Biochemistry, 2025)

Battery fault diagnosis methods for electric vehicle lithium-ion batteries: Correlating codes and battery management system - Naresh G; T. Praveenkumar; Dinesh Kumar Madheswaran; Edwin Geo Varuvel; Arivalagan Pugazhendhi; Mohanraj Thangamuthu; S. Jenoris Muthiya (Process Safety and Environmental Protection, 2025)

Design of a novel green synthesized ZVS/S-rGO -Deinococcus radiodurans R1 chitosan hydrogel beads for enhanced recovery of europium - Ananya Jena; Naresh Kumar Sahoo; Prasanta Kumar Sahoo; Soumya Mishra; Prangya Ranjan Rout; Yulin Zhong (Journal of Cleaner Production, 2025)

Assessment of Water Quality Status and Heavy Metals Contamination in River Kali-East, India using Pollution Indexes and Health Hazards - Bhanu Pratap; Sampurna Nand; Saroj Kumar; Pradeep Kumar; Ram Naresh Bharagava; Venkatesh Dutta (Water, Air, & Soil Pollution, 2025)

An Effective Barrier Coating Technology Against Premature Bolt Failures in Underground Mines - Honghao Chen; Önder Kimyon; Cindy Gunawan; Hamed Lamei Ramandi; Peter Craig; Renxun Chen; Imrana Kabir; Naresh Kumar; Michael Manefield; Alan Crosky; Ismet Canbulat; Serkan Saydam (Rock Mechanics and Rock Engineering, 2025)
Significant safety and economic consequences accompany the premature failure of bolts, posing sustainability challenges for mining operations. Previous studies have indicated that hydrogen-induced stress corrosion cracking (HISCC), primarily influenced by microbial activities termed microbiologically influenced stress corrosion cracking (MISCC), stands as a major contributor to the premature failure of bolts in underground mines. Presently, an effective mechanism to mitigate these premature failures is lacking. In this study, multiple commercially available coatings undergo testing to assess their susceptibility and suitability in preventing HISCC and MISCC. Additionally, a purpose-developed coating is examined. The results reveal that the tested commercially available coatings either fail to prevent these types of corrosion or are unsuitable for the intricate conditions within underground mines. The laboratory results show the coating has a significant anti-acidic corrosion and anti-MISCC performance. Conversely, the coating formulated in this study successfully averts both MISCC and HISCC, proving its applicability within the complex geological environments prevalent in mines. This breakthrough offers a promising solution to mitigate premature bolt failures in complex underground geological environments. The developed coating presents a viable way forward for enhancing safety, reducing economic losses, and improving the overall sustainability of mining operations.

Transcriptome Analysis Reveals Differential Gene Regulation in Ovarian Tissues of Anabas testudineus (Bloch, 1792) in Response to Insecticide, Monocrotophos - Siyag A. Dhere; Pokanti Vinay Kumar; Kiran D. Rasal; Sujata Mohapatra; Prachi Asgolkar; Manohar Vasam; Sheetal Vanjre; Priyanka S. S.; Manoj P. Brahmane; Arvind Sonwane; Rajesh Kumar; Naresh S. Nagpure; et al. (Marine Biotechnology, 2025)

Unlocking the potential of fishery waste: exploring diverse applications of fish protein hydrolysates in food and nonfood sectors - Anand Vaishnav; Jham Lal; Naresh Kumar Mehta; Saswat Mohanty; Krishan Kumar Yadav; Mocherla Bhargavi Priyadarshini; Payel Debbarma; Nongthongbam Sureshchandra Singh; Bikash Kumar Pati; Soibam Khogen Singh (Environmental Science and Pollution Research, 2025)

Estimating coal proximate parameters and Gross Calorific Value from geophysical logs in Talcher coalfield using multi-layer perceptron, multi-output regression, and ensemble machine learning - Thinesh Kumar; Naresh Kumar Seelam; G Srinivasa Rao (Journal of Earth System Science, 2025)

Tomographic evidence for segmentation of the Main Himalayan Thrust in the Uttarakhand Himalaya - Jyotima Kanaujia; M. Ravi Kumar; Naresh Bandari; R. Vijayaraghavan (Tectonophysics, 2025)

Methodological framework for reliable high-resolution regional wave climate projections using statistical and dynamical techniques - Naresh Kumar Goud Lakku; Manasa Ranjan Behera (Ocean Engineering, 2025)

Estimation of source parameters and scaling relationship of the local earthquakes in the Central Seismic gap NW Himalaya, India - Abhishek Kumar Gupta; Anil Tiwari; Naresh Kumar; Ajay Paul; Kalachand Sain; Dilip Kumar Yadav; Ashish Pal; Debonil Baruah (Journal of Asian Earth Sciences, 2025)

Impact of microwave-assisted acid extraction (MW-AAE) methods on simultaneous ICP-MS analysis of multi-elements in edibles besides associated greenness and human health risk assessment - Naresh Pothuraju; Harish Kumar Pogula; Rushikant Jagdale; Udaya Kumar Vadla; Rahul Laxman Gajbhiye; Vipan Kumar Parihar; Ravichandiran Velayutham; Ramalingam Peraman (Environmental Monitoring and Assessment, 2025)

Polyphasic characterization of 15 heterocytous cyanobacterial isolates from different habitats of India and description of 9 novel species belonging to the genera Desikacharya, Aliinostoc, and Desmonostoc - Sagarika Pal; Aniket Saraf; Naresh Kumar; Harsh Pant; Shaikh Soyeb Akhatar Badruddin; Shaikh Maksood Ali Sajibulla; Shaikh Kalamuddin Nijamuddin; Ambika Prajapati; Utkarsh Talukdar; Niraj Kohar; Arush Singh; Pampi Sarmah; et al. (Algal Research, 2025)

ERα, HER-2, pan-RAS, p53, and aromatase expression in spontaneous malignant canine mammary tumors: Prognostic relevance and association with clinicohistological parameters - Siddharth Gautam; Kuldip Gupta; Vinodhkumar Obli Rajendran; Karam Chand; Chitra Joshi; Naresh Kumar Sood (Research in Veterinary Science, 2025)

Scaffolds imparting anthelmintic activity: recent advancements and SAR studies - Pawan Kumar; Rohit Bhatia; Naresh Kumar Rangra (Molecular Diversity, 2025)

Effects of Dietary Protein Levels on Growth Performance, Plasma Parameters, and Digestive Enzyme Activities in Different Intestinal Segments of Megalobrama amblycephala at Two Growth Stages - Wuxiao Zhang; Silei Xia; Bo Liu; Hongyan Tian; Fei Liu; Wenping Yang; Yebing Yu; Caiyuan Zhao; Naresh Kumar Dewangan; Aimin Wang; Tao Teng (Fishes, 2025)
An 8-week rearing trial was designed to estimate the dietary protein requirement and evaluate the effects of dietary protein on growth performance, plasma parameters, and digestive enzyme activities of blunt snout bream at two growth stages. Six practical diets were prepared to feed two sizes of fish (larger fish: initial weight of 153.69 ± 0.85 g; smaller fish: initial weight of 40.89 ± 0.28 g) with graded protein levels (26%, 28%, 30%, 32%, 34%, and 36%). Our results show that the final weight, weight gain (WG), and specific growth rate (SGR) of the fish initially rose to peak values and then declined as the dietary protein levels increased. The higher WG and SGR were recorded in the larger fish fed diets containing 30%, 32%, and 34% protein, and in the smaller fish fed a 30% protein diet, all significantly higher than those in the control group (p 0.05). The plasma total protein (TP) content was highest at both growth stages in fish fed a 30% protein diet (p 0.05). Protease activity in the fish foregut at both growth stages peaked in the 32% protein group (p 0.05). The dietary protein levels had no significant effect on lipase activity in the foregut, midgut, or hindgut, or on amylase activity in the foregut or midgut of the fish at the two growth stages (p > 0.05). However, hindgut amylase activity was highest in the control group of the smaller fish (p

Characterization of PFOA isomers from PFAS precursors and their reductive defluorination - Jun Sun; Wanutcha Lorpaiboon; Nicholas Fox; Adele Jones; Junming Ho; Michael J. Manefield; Naresh kumar; Denis O'Carroll; Matthew Lee (Water Research, 2025)

Wastewater based measures of COVID-19 and associations with children's absenteeism at grade schools - Helena M. Solo-Gabriele; Gabriela Guevara; Naresh Kumar; Ayaaz Amirali; Kristina M. Babler; Cynthia C. Beaver; Samuel Comerford; Maria Ferraris; Natasha Schaefer Solle; Mark E. Sharkey; Lisa Gwynn (Science of The Total Environment, 2025)

Long-term effects of cycle time and volume exchange ratio on poly(3-hydroxybutyrate-co-3-hydroxyvalerate) production from food waste digestate by Haloferax mediterranei cultivated in sequencing batch reactors for 450 days - Xueyao Zhang; Zhaohui An; Jiefu Wang; Stephanie Lansing; Naresh Kumar Amradi; Md. Sazzadul Haque; Zhi-Wu Wang (Bioresource Technology, 2025)

A Comparative Study of Machine Learning Models for Daily and Weekly Rainfall Forecasting - Vijendra Kumar; Naresh Kedam; Ozgur Kisi; Saleh Alsulamy; Khaled Mohamed Khedher; Mohamed Abdelaziz Salem (Water Resources Management, 2025)
Accurate rainfall forecasting is crucial for various sectors across diverse geographical regions, including Uttarakhand, Uttar Pradesh, Haryana, Punjab, Himachal Pradesh, Madhya Pradesh, Rajasthan, and the Union Territory of Delhi. This study addresses the need for precise rainfall predictions by bridging the gap between localized meteorological data and broader regional influences. It explores how rainfall patterns in neighboring states affect Delhi's precipitation, aiming to improve forecasting accuracy. Historical rainfall data from neighboring states over four decades (1980–2021) were collected and analyzed. The study employs a dual-model approach: a daily model for immediate rainfall triggers and a weekly model for longer-term trends. Several machine learning algorithms, including CatBoost, XGBoost, ElasticNet, Lasso, LGBM, Random Forest, Multilayer Perceptron, Ridge, Stochastic Gradient Descent, and Linear Regression, were used in the modeling process. These models were rigorously assessed based on performance metrics from training, validation, and testing datasets. For daily rainfall forecasting, CatBoost, XGBoost, and Random Forest emerged as top performers, showcasing exceptional accuracy and pattern-capturing capabilities. In weekly rainfall forecasting, XGBoost consistently achieved near-perfect accuracy with an R 2 value of 0.99, with Random Forest and CatBoost also demonstrating strong performance. The study provides valuable insights into how climate patterns in neighboring states influence Delhi's weather, leading to more reliable and timely rainfall predictions.

Greenness assessment for the control of trace-level genotoxic process impurities in Vildagliptin by liquid chromatography with mass spectrometry - Vaishnavi Chintala; Ravindra Mallavarapu; Naresh Kumar Katari; Siva Krishna Muchakayala; Vishnu Murthy Marisetti (Sustainable Chemistry and Pharmacy, 2024)

Low cost fabrication of continuous flow optofluidic microreactor for efficient dye degradation using graphene QDs@MOF (Ti) photocatalyst - Gulshan Verma; Prashanth Venkatesan; Deblina Roy; Parthivi Aloni; Naresh Kumar Dega; Ankur Gupta (Environmental Research, 2024)

Differential regulation of glucosinolate-myrosinase mediated defense determines host-aphid interaction in Indian mustard Brassica juncea L. - Ashakiran Loitongbam; Naresh Kumar Samal; Nikhil Ram Kumar; Satish Kumar; Muthuganeshan Annamalai; Aditi Kundu; Sabtharishi Subramanian; Ramcharan Bhattacharya (Molecular Biology Reports, 2024)

Physiological Responses to Acute Heat Stress in Rohu, Labeo rohita: Insights from Liver Proteomics - Mohan R. Badhe; Priyanka Das; Sonalina Sahoo; Anirban Paul; Pramoda Kumar Sahoo; R. Rajendra Kumar Reddy; Amol R. Suryawanshi; Priyanka C. Nandanpawar; Kanta Das Mahapatra; Naresh S. Nagpure; Mukunda Goswami; Jyotirmaya Mohanty (Marine Biotechnology, 2024)

Generic AAA Architecture for Geospatial Web Service Dissemination Based on Open-Source API Gateway - N. Naresh; M. Nitin; M. Aarathi; P. Aravinda Kumar; S. S. Rajshekar; S. Srinivasa Rao (Journal of Geovisualization and Spatial Analysis, 2024)

Drought assessment through multiple indicators for Karnataka state, India - Neha Singhal; Manoj Khanna; Man Singh; Vijay Kumar Prajapati; Laxya Gupta; D. K. Singh; S. Naresh Kumar; Vinay Kumar Sehgal (Environmental Monitoring and Assessment, 2024)

Correction to: Predicting the potential habitat of bears under a changing climate in Nepal - Rishi Baral; Binaya Adhikari; Rajan Prasad Paudel; Rabin Kadariya; Naresh Subedi; Bed Kumar Dhakal; Michito Shimozuru; Toshio Tsubota (Environmental Monitoring and Assessment, 2024)

Tilapia lake virus: understanding incidence, enhancing resistance, and exploring seaweed therapies - Sourabh Debbarma; Nitesh Kumar Yadav; Ng Chinglembi Devi; Bagthasingh Chrisolite; Yilbong Yirang; Dharmendra Kumar Meena; Soibam Khogen Singh; Naresh Kumar Mehta; Bhargavi Priyadarshini Mocherla (Aquaculture International, 2024)

An insight into the ethnopharmacological importance of Indian subcontinent medicinal plant species of Rubiaceae family - Debajyoti Roy; Seema Brar; Rohit Bhatia; Naresh Kumar Rangra (Advances in Traditional Medicine, 2024)

Understanding the role of topography, climate, and sediment transport dynamics in flash flood hazards along the Dhauli Ganga River of northwest Himalaya, India - Sameeksha Kaushik; Dhirendra Singh Bagri; Yaspal Sundriyal; Sandeep Kumar; Neha Chauhan; Naresh Rana (Journal of Earth System Science, 2024)

Evaluating landslide hazard, vulnerability, and risk using machine learning; A case study from the Alaknanda Valley, NW Himalaya - Yaspal Sundriyal; Sandeep Kumar; Sameeksha Kaushik; Neha Chauhan; Robert Wasson; Shravi Agarwal; Sanjeev Kumar; Vipin Kumar; Dhirendra Singh Bagri; Naresh Rana; Anirudh Chouhan (Environment, Development and Sustainability, 2024)

Open windrow composting of lignocellulosic crop residues and neem litter: Accounting for reactive nitrogen and greenhouse gas emissions - Helen Mary Rose; Niveta Jain; Shiva Dhar Misra; Om Kumar; Komal Prasad; Tapan Jyoti Purakayastha; Arti Bhatia; Soora Naresh Kumar; Shruti Sethi (Journal of Cleaner Production, 2024)

Epidemiology, genetic characterization and population structure analysis of lumpy skin disease virus from North India - Pallavi Moudgil; Ramesh Kumar; Punit Jhandai; Sameer Kamboj; Khushbu Bishnoi; Kushal Grakh; Renu Gupta; Rajesh Khurana; Naresh Jindal (Tropical Animal Health and Production, 2024)

Comparative Preclinical Pharmacokinetics and Disposition of Favipiravir Following Pulmonary and Oral Administration as Potential Adjunct Therapy Against Airborne RNA Viruses - Venkata Siva Reddy Devireddy; Hasham Shafi; Sonia Verma; Sanjay Singh; J. V. U. S. Chakradhar; Naresh Kothuri; Himanshu Bansode; Sunil Kumar Raman; Deepak Sharma; Lubna Azmi; Rahul Kumar Verma; Amit Misra (Pharmaceutical Research, 2024)

Predicting the potential habitat of bears under a changing climate in Nepal - Rishi Baral; Binaya Adhikari; Rajan Prasad Paudel; Rabin Kadariya; Naresh Subedi; Bed Kumar Dhakal; Michito Shimozuru; Toshio Tsubota (Environmental Monitoring and Assessment, 2024)
In Nepal, the distributions of three bear species vary: sloth bears ( Melursus ursinus ) in the lowlands, Asiatic black bears ( Ursus thibetanus ) in the mid-hills, and brown bears (Ursus arctos) in the high Himalayas. We utilized 179 occurrence points for sloth bears, 199 for Asiatic black bears, and 41 points for brown bears to construct a habitat model incorporating climate and topographic variables. Employing various species distribution modeling algorithms in BIOMOD2, the model predicts suitable habitats spanning 10,971.75 km 2 for sloth bears; 29,470.75 km 2 for Asiatic black bears; and 6152.97 km 2 for brown bears. Within protected areas, the habitat for sloth bears is 4120.56 km 2 , that for Asiatic black bears is 9688.67 km 2 , and that for brown bears is 4538.67 km 2 . Chitwan National Park emerged as the prime sloth bear habitat with a core area of 918.55 km 2 and a buffer zone of 726.485 km 2 . The Annapurna Conservation Area was deemed suitable for Asiatic black bears and brown bears, covering 2802.23 km 2 and 2795.91 km 2 , respectively. The models projected a significant reduction in the habitat of these bear species both inside and outside protected areas. As predicted under the Shared Socioeconomic Pathways (SSP)2–4.5 scenario, sloth bears may experience 54.9% (2050) and 44.7% (2070) losses, respectively, of habitat; Asiatic black bears, 11.2% (2050) and 16.8% (2070); and brown bears, 68.41% (2050) and 82.20% (2070) losses. The overlap between sloth bears and black bears spans 38.7 km 2 , and that between brown bears and black bears is 26.6 km 2 . Notably, all three bear species exhibited suitability correlations with the intermediate temperature of the driest quarter. Examining current and projected habitats provides essential information for guiding conservation strategies and ensuring the conservation of these bear species in the face of climate change.

Debris flow in indian himalaya: A threat to emerging infrastructure - Neha Chauhan; Vipin Kumar; Yaspal Sundriyal; Sameeksha Kaushik; Srikrishnan Siva Subramanian; Raquel Melo; Naresh Rana (Bulletin of Engineering Geology and the Environment, 2024)

An improved hybrid model for shoreline change - Naresh Kumar Goud Lakku; Piyali Chowdhury; Manasa Ranjan Behera (Frontiers in Marine Science, 2024)
Predicting the nearshore sediment transport and shifts in coastlines in view of climate change is important for planning and management of coastal infrastructure and requires an accurate prediction of the regional wave climate as well as an in-depth understanding of the complex morphology surrounding the area of interest. Recently, hybrid shoreline evolution models are being used to inform coastal management. These models typically apply the one-line theory to estimate changes in shoreline morphology based on littoral drift gradients calculated from a 2DH coupled wave, flow, and sediment transport model. As per the one-line theory, the calculated littoral drift is uniformly distributed over the active coastal profile. A key challenge facing the application of hybrid models is that they fail to consider complex morphologies when updating the shorelines for several scenarios. This is mainly due to the scarcity of field datasets on beach behavior and nearshore morphological change that extends up to the local depth of closure, leading to assumptions in this value in overall shoreline shift predictions. In this study, we propose an improved hybrid model for shoreline shift predictions in an open sandy beach system impacted by human interventions and changes in wave climate. Three main conclusions are derived from this study. First, the optimal boundary conditions for modeling shoreline evolution need to vary according to local coastal geomorphology and processes. Second, specifying boundary conditions within physically realistic ranges does not guarantee reliable shoreline evolution predictions. Third, hybrid 2D/one-line models have limited applicability in simple planform morphologies where the active beach profile is subject to direct impacts due to wave action and/or human interventions, plausibly due to the one-line theory assumption of a constant time-averaged coastal profile. These findings provide insightful information into the drivers of shoreline evolution around sandy beaches, which have practical implications for advancing the shoreline evolution models.

Sorption of PFOS onto polystyrene microplastics potentiates synergistic toxic effects during zebrafish embryogenesis and neurodevelopment - Priya Gupta; Archisman Mahapatra; Bharat Manna; Anjali Suman; Shubhendu Shekhar Ray; Naresh Singhal; Rahul Kumar Singh (Chemosphere, 2024)

Waste-to-energy technologies: Integrating anaerobic digestion, microbial electrolysis cells, hydrodynamic cavitation, and electrocoagulation - Kirkland Mahoney; Stephanie Lansing; Naresh Kumar Amradi; Derrick Sanders; Gregory Loraine; Amro Hassanein (Journal of Cleaner Production, 2024)

Neoproterozoic crustal evolution of Indo-Australo-Antarctic Suture domain and Gamburtsev Subglacial Mountains, East Antarctica: Insights from offshore sediments - Rashmi Gupta; Mayuri Pandey; Devsamridhi Arora; Akash K. Pandey; Naresh C. Pant; K. Batuk Joshi; Pankaj Kumar; M. Satyanarayanan; Atul Singh (Gondwana Research, 2024)

Effect of potassium persulphate-induced microwave pretreatment for cost-effective sludge solubilization and bioenergy recovery - Yukesh Kannah Ravi; S. Kavitha; Arulazhagan Pugazhendi; R. Naresh Kumar; J. Rajesh Banu (Chemical Engineering Journal, 2024)

Nutrient removal in floating and vertical flow constructed wetlands using aluminium dross: An innovative approach to mitigate eutrophication - Yamini Mittal; Pratiksha Srivastava; Naresh Kumar; Bankim Chandra Tripathy; Fernando Martinez; Asheesh Kumar Yadav (Bioresource Technology, 2024)

Insights to therapeutic potentials, pharmaceutical formulations, chemistry and analytical methods of catechin - Divya Shikha; Amandeep Singh; Naresh Kumar Rangra; Vikramdeep Monga; Rohit Bhatia (Phytochemistry Reviews, 2024)

Elucidating the Defence Response of Wheat Mutants Developed for augmenting Terminal Heat Stress Tolerance and Improved Grain-Quality - Ranjeet R. Kumar; Suman Bakshi; Suneha Goswami; Sudhir Kumar; Vinutha Thimmegowda; Sanjay J. Jambhulkar; Gyan P. Mishra; Gyanendra K. Rai; Soora Naresh Kumar; Bhupinder Singh; Gyanendra P. Singh; Viswanathan Chinnusamy; et al. (Journal of Plant Growth Regulation, 2024)

A Critical Insight into the Breeding for Resistance to Bacterial Diseases in Pepper (Capsicum spp.) - Satyaprakash Barik; Susheel Kumar Sharma; Ponnam Naresh; Ajay Kumar Karna; Sangeetha Ganesan; Licon Kumar Acharya; Gobinda Chandra Acharya (Journal of Crop Health, 2024)

Comparative proteomic analysis provides insight into the key proteins involved in novel stem-physical-strength-mediated resistance (SPSMR) mechanism against Sclerotinia sclerotiorum in Brassicaceae - Manjeet Singh; Ram Avtar; Nita Lakra; Neeraj Kumar; Mahavir Bishnoi; Rakesh Punia; Raju Ram Choudhary; Nisha Kumari; Naresh Naresh; Ankit Dhillon (European Journal of Plant Pathology, 2024)

Effects of lateral spacings and irrigation water quality on plant growth and yield parameters of onion in the semi‐arid region of India - Mukesh Kumar; Ram Naresh; Darshana Duhan; Kuldeep Singh; Mukesh Kumar Mehla; Raj Kumar Jhorar (Irrigation and Drainage, 2024)
Field experiments were conducted to investigate an appropriate saline water management strategy to enhance the yield and irrigation water use efficiency (IWUE) of drip‐irrigated onion. The effects on soil water–salt dynamics, growth parameters, IWUE and yield were assessed under different lateral spacings and irrigation treatments. The different treatments comprised two lateral spacings (45 and 60 cm) and four irrigation treatments (canal water, C; conjunctive use of canal and saline water in a 1:1 ratio, C 1 S 1 ; in a 1:2 ratio, C 1 S 2 ; and saline water, S). The results show that soil moisture content decreased vertically downwards and radially outwards in all treatments, whereas soil salinity increased and decreased with increasing radial distance and soil depth, respectively, throughout the soil profile irrespective of the lateral spacing and irrigation treatments. The maximum yield and IWUE were observed at 45‐cm lateral spacing for treatment C, followed by C 1 S 1 , C 1 S 2 and S. It was concluded that the C 1 S 1 treatment can be employed successfully for onion cultivation in sandy loam soil without any significant reduction in yield. The present study highlights the significance of irrigation treatments and lateral spacing for maximum production, which may be used as a baseline/guideline to increase the income of onion growers/farmers in semi‐arid regions.

Fat Uptake Reduction During Deep-Fat Frying of Fish Fillets Coated with Soy Protein Isolate Edible Coating - Kumar Gaurav; Naresh Kumar Mehta; M. Bhargavi Priyadarshini; Prasenjit Pal; Nilesh Prakash Nirmal; Sanjeev Sharma; Anand Vaishnav (Journal of Aquatic Food Product Technology, 2024)

Formaldehyde contamination in seafood industry: an update on detection methods and legislations - Naresh Kumar Mehta; Anand Vaishnav; Mocherla Bhargavi Priyadarshini; Payel Debbarma; Mohammad Sazedul Hoque; Pronoy Mondal; Mahmud Ab Rashid Nor-Khaizura; Gioacchino Bono; Pankaj Koirala; Aikkarach Kettawan; Nilesh Prakash Nirmal (Environmental Science and Pollution Research, 2024)

Nurturing hope: Uncovering the potential of herbal remedies against amyotrophic lateral sclerosis - Mukta Gupta; Md Sadique Hussain; Riya Thapa; Asif Ahmad Bhat; Naresh Kumar (PharmaNutrition, 2024)

Correction: Toxicity of ultrafine particles during Diwali’s firework: an in-vitro study of A549 cells - Dudun Mehta; Naresh Kumar; Arun Srivastava (Toxicology and Environmental Health Sciences, 2024)

Toxicity of ultrafine particles during Diwali’s firework: an in-vitro study of A549 cells - Dudun Mehta; Naresh Kumar; Arun Srivastava (Toxicology and Environmental Health Sciences, 2024)

Comparative transcriptome profile of embryos at different developmental stages derived from somatic cell nuclear transfer (SCNT) and in-vitro fertilization (IVF) in riverine buffalo (Bubalus bubalis) - Deepak Kumar; Manish Tiwari; Pallavi Goel; Manoj Kumar Singh; Naresh Lala Selokar; Prabhat Palta (Veterinary Research Communications, 2024)

Scoparone chemical modification into semi-synthetic analogues featuring 3-substitution for their anti-inflammatory activity - Chetan Kumar; Pankaj Chibber; Ritu Painuli; Syed Assim Haq; Ram A. Vishwakarma; Gurdarshan Singh; Naresh K. Satti; Ravindra S. Phatake (Molecular Diversity, 2024)

Trait phenotyping in an ancient Indian landrace of wheat Triticum sphaerococcum under optimum, terminal heat stress and deficit irrigation conditions - Kiran B. Gaikwad; Ankit Dawar; Akash Singh; Prashanth Babu; Manjeet Kumar; Naresh Kumar; Amit Kumar Mazumder; Rakesh Kumar; Anjan Kumar Pradhan; Rihan Ansari; Nasreen Saifi; Rajbir Yadav (Genetic Resources and Crop Evolution, 2024)

Sub-surface drip-fertigation and legume residue improved maize yield and nitrogen use - Arjun Singh; Anchal Dass; Susama Sudhishri; V. K. Singh; Kapila Shekhawat; M. C. Meena; R. N. Sahoo; Soora Naresh Kumar; P. K. Upadhyay; Shiva Dhar; Kadagonda Nithinkumar (Nutrient Cycling in Agroecosystems, 2024)

Soluble metal porphyrins - Zero-valent zinc system for effective reductive defluorination of branched per and polyfluoroalkyl substances (PFASs) - Jun Sun; Tsz Tin Yu; Maryam Mirabediny; Matthew Lee; Adele Jones; Denis M. O'Carroll; Michael J. Manefield; Priyank V. Kumar; Russell Pickford; Zeno Rizqi Ramadhan; Saroj Kumar Bhattacharyya; Björn Åkermark; et al. (Water Research, 2024)

Solid phase speciation controls copper mobilisation from marine sediments by methanobactin - Danielle D. Rushworth; Walter D.C. Schenkeveld; Naresh Kumar; Vincent Noël; Jannes Dewulf; Niels A.G.M. van Helmond; Caroline P. Slomp; Moritz F. Lehmann; Stephan M. Kraemer (Science of The Total Environment, 2024)

Synthesis of Cu (II) and Zn (II) Complexes of a Quinoline Based Flexible Amide Receptor as Fluorescent Probe for Dihydrogen Phosphate and Hydrogen Sulphate and Their Antibacterial Activity - Sovan Dey; Sandip Ghosh; Arindam Das; Ram Naresh Yadav; Rinku Chakrabarty; Smriti Pradhan; Dipanwita Saha; Ashok Kumar Srivastava; Md. Firoj Hossain (Journal of Fluorescence, 2024)

Climatology of thermodynamic indices and background synoptic conditions responsible for severe convection during pre‐ to post‐monsoon seasons over Indian region - A. Madhulatha; M. Mohapatra; K. Sathi Devi; D. R. Pattanaik; M. Rajeevan; Anand Kumar Das; R. K. Jenamani; Naresh Kumar (International Journal of Climatology, 2024)
To investigate the mechanisms responsible for severe convection linked with a variety of mesoscale, synoptic systems over the Indian region, a preliminary analysis is conducted. Using IMD RSRW/Reanalysis (ERA5)/Lightning (TRMM LIS) products both local‐scale thermodynamics and large‐scale background conditions responsible for the major lightning hot spots in different seasons are investigated. In the pre‐monsoon season, high lightning activity over NE Indian region is due to moisture intrusion by south‐westerly at lower levels (warm air advection), along with mid‐level north westerlies (cold air advection) which favour the low‐level convergence and upper‐level divergence. SCS over south India are mainly attributed to wind discontinuity over the region. During monsoon season major lightning activity in NW India is due to the presence of heat low and the rest of the country less intense SCS activity is evident due to high wind shear conditions in connection with low‐level (westerly) and upper‐level (easterly jet stream). In the post‐monsoon season, major lightning in south India are due to the prevailing north‐easterlies and in north India, the activity is attributed to the passage of western disturbance (WD). Station plot analysis suggests the varied distribution of thermodynamic indices season/region‐wise due to the diverse background forcing. Correlation analysis between the lightning and thermodynamic indices suggests that more skillful indices are KI (~0.7 to 0.8), precipitable water (PPW) (~0.8) (pre‐monsoon, monsoon) and (PPW) (~0.8), convective available potential energy (CAPE) (~0.6) in post monsoon over respective lightning hot‐spot regions. Independent verification using Wyoming data/reanalysis for different case studies suggests that monitoring the monthly thresholds of highly correlated indices provides a helpful proxy to operationally forecast the severe convective systems (season/region). Mean Equivalent potential temperature, and mixing ratio in mixed layer has shown reasonable association with the lightning occurrence over all lightning hot spot regions which are implemented in the IMD GFS and IMD WRF models.

Digital hemispherical photographs and Sentinel-2 multi-spectral imagery for mapping leaf area index at regional scale over a tropical deciduous forest - Mukunda Dev Behera; J. S. R. Krishna; Somnath Paramanik; Shubham Kumar; Soumit K. Behera; Sonik Anto; Shiv Naresh Singh; Anil Kumar Verma; Saroj K. Barik; Manas Ranjan Mohanta; Sudam Charan Sahu; Chockalingam Jeganathan; et al. (Tropical Ecology, 2024)

Mathematical vs. machine learning models for particle size distribution in fragile soils of North-Western Himalayas - Owais Bashir; Shabir Ahmad Bangroo; Shahid Shuja Shafai; Tajamul Islam Shah; Shuraik Kader; Lizny Jaufer; Nicola Senesi; Alban Kuriqi; Negar Omidvar; Soora Naresh Kumar; Ayyanadar Arunachalam; Ruby Michael; et al. (Journal of Soils and Sediments, 2024)
Purpose Particle size distribution (PSD) assessment, which affects all physical, chemical, biological, mineralogical, and geological properties of soil, is crucial for maintaining soil sustainability. It plays a vital role in ensuring appropriate land use, fertilizer management, crop selection, and conservation practices, especially in fragile soils such as those of the North-Western Himalayas. Materials and methods In this study, the performance of eleven mathematical and three Machine Learning (ML) models used in the past was compared to investigate PSD modeling of different soils from the North-Western Himalayan region, considering that an appropriate model must fit all PSD data. Results and discussion Our study focuses on the significance of evaluating the goodness of fit in particle size distribution modeling using the coefficient of determination (R 2 adj = 0.79 to 0.45), the Akaike information criterion (AIC = 67 to 184), and the root mean square error (RMSE = 0.01 to 0.09). The Fredlund, Weibull, and Rosin Rammler models exhibited the best fit for all samples, while the performance of the Gompertz, S-Curve, and Van Genutchen models was poor. Of the three ML models tested, the Random Forest model performed the best (R 2 = 0.99), and the SVM model was the lowest (R 2 = 0.95). Thus, the PSD of the soil can be best predicted by ML approaches, especially by the Random Forest model. Conclusion The Fredlund model exhibited the best fit among mathematical models while random forest performed best among the machine learning models. As the number of parameters in the model increased better was the accuracy.

Machine learning-based potential loss assessment of maize and rice production due to flash flood in Himachal Pradesh, India - Swadhina Koley; Soora Naresh Kumar (Environmental Monitoring and Assessment, 2024)

Unveiling machine learning's impact on in vitro callogenesis optimization in Crocus sativus L - Melina Sarabandi; Rajesh Kumar Singh; Siamak Kalantari; Majid Shokrpour; Ram Naresh; Shahin Rafiee (South African Journal of Botany, 2024)

Assessment of radon transportation and uranium content in the tectonically active zone of Himalaya, India - Rohit Singh Sajwan; Veena Joshi; Taufiq Ahamad; Naresh Kumar; Priyanka Parmar; Manoj Kumar Jindal (Science of The Total Environment, 2024)

Processes responsible for mixed layer variations near mesoscale eddies in the Bay of Bengal - Venkata Sai Gulakaram; Naresh Krishna Vissa; Prasad Kumar Bhaskaran (Ocean Dynamics, 2024)

Climate change effects on aquaculture production and its sustainable management through climate-resilient adaptation strategies: a review - Nitesh Kumar Yadav; Arun Bhai Patel; Soibam Khogen Singh; Naresh Kumar Mehta; Vishwajeet Anand; Jham Lal; Debojit Dekari; Ng Chinglembi Devi (Environmental Science and Pollution Research, 2024)

Modelling of source parameters of local earthquakes and seismotectonic implications in Siang Valley, NE India - Ashish Pal; Dilip Kumar Yadav; Naresh Kumar; Abhishek Kumar Gupta; Ajay Paul; H C Nainwal (Journal of Earth System Science, 2024)

Microbial strategies for copper pollution remediation: Mechanistic insights and recent advances - Abdulrab Ahmed M. Alkhanjaf; Sonu Sharma; Monu Sharma; Raman Kumar; Naresh Kumar Arora; Brajesh Kumar; Ahmad Umar; Sotirios Baskoutas; Tapan Kumar Mukherjee (Environmental Pollution, 2024)

Characterization of microplastics in outdoor and indoor air in Ranchi, Jharkhand, India: First insights from the region - Shreya Nandi; Radhakrishnan Naresh Kumar; Abisheg Dhandapani; Jawed Iqbal (Environmental Pollution, 2024)

Clinico-Etiopathogenesis of Vitamin B12, Folic Acid and Iron Deficiency in Severe Acute Malnutrition Children: A Tertiary Care Hospital Experience from Central India - Priyanka Shukla; Sanjay Kumar Pandey; Jyoti Singh; Naresh Bajaj; Gaurav Tripathi; Sudhakar Dwivedi (Indian Journal of Clinical Biochemistry, 2024)

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

Thread-powered cell lysis and isotachophoresis: unlocking microbial DNA for diverse molecular applications - Rishabh Garg; Aharnish Maurya; Naresh Kumar Mani; Dinesh Prasad (World Journal of Microbiology and Biotechnology, 2024)

Quantification and characterization of airborne microplastics in the coastal area of Terengganu, Malaysia - Naresh Kumar Chenappan; Yusof Shuaib Ibrahim; Sabiqah Tuan Anuar; Ku Mohd Kalkausar Ku Yusof; Maisarah Jaafar; Fatimah Ahamad; Wan Zuriana Wan Sulaiman; Noorlin Mohamad (Environmental Monitoring and Assessment, 2024)

Aluminium dross waste utilization for phosphate removal and recovery from aqueous environment: Operational feasibility development - Yamini Mittal; Pratiksha Srivastava; Bankim Chandra Tripathy; Nabin Kumar Dhal; Fernando Martinez; Naresh Kumar; Asheesh Kumar Yadav (Chemosphere, 2024)

Evaluation of PM2.5 spatio-temporal variability and hotspot formation using low-cost sensors across urban-rural landscape in lucknow, India - Sandeep Madhwal; Sachchida Nand Tripathi; Michael Howard Bergin; Prakash Bhave; Benjamin de Foy; T.V. Ramesh Reddy; Sandeep Kumar Chaudhry; Vaishali Jain; Naresh Garg; Paresh Lalwani (Atmospheric Environment, 2024)

Multi-model exploration of groundwater quality and potential health risk assessment in Jajpur district, Eastern India - Sushree Sabinaya; Biswanath Mahanty; Prangya Ranjan Rout; Sangeeta Raut; Sunil Kumar Sahoo; Vivekanand Jha; Naresh Kumar Sahoo (Environmental Geochemistry and Health, 2024)

Valorizing waste to wealth: a blue revolution in environmental science - Dharmendra Kumar Meena; K. N. Mohanta; Amiya Kumar Sahoo; Soibam Khogen Singh; Naresh Kumar Mehta (Environmental Science and Pollution Research, 2024)

Insights into Translational and Biomedical Applications of Hydrogels as Versatile Drug Delivery Systems - Ramesh Kohar; Maitrayee Ghosh; Jyotiram A. Sawale; Amandeep Singh; Naresh Kumar Rangra; Rohit Bhatia (AAPS PharmSciTech, 2024)

A systematic review on potential microbial carbohydrases: current and future perspectives - Dilshad Begum Golgeri M.; Sikandar I. Mulla; Zabin K. Bagewadi; Swati Tyagi; Anyi Hu; Swati Sharma; Muhammad Bilal; Ram Naresh Bharagava; Luiz Fernando R. Ferreira; Dummi Mahadevan Gurumurthy; Ashok Kumar Nadda (Critical Reviews in Food Science and Nutrition, 2024)

Co-infection of mud crab Reovirus (MCRV) and Staphylococcus saprophyticus in giant mud crab, Scylla serrata (Forsskal, 1775) - Anisha Shafni John; Ayyaru Gopalakrishnan; Savva Sravani; Naresh Kumar Dewangan; Muhil Vannan Seralathan; Narayanasamy Marimuthu Prabhu (Aquaculture, 2024)

Evaluation of postnatal growth, hematology, telomere length and semen attributes of multiple clones and re-clone of superior buffalo breeding bulls - P.S. Yadav; Dharmendra Kumar; Monika Saini; R.K. Sharma; Seema Dua; Naresh L. Selokar; Sonu Bansal; Meeti Punetha; Akanksha Gupta; Rajesh Kumar; Pradeep Kumar (Theriogenology, 2024)

An integrated approach of machine learning and remote sensing for evaluating landslide hazards and risk hotspots, NW Himalaya - Yaspal Sundriyal; Sandeep Kumar; Neha Chauhan; Sameeksha Kaushik; Vipin Kumar; Naresh Rana; Robert Wasson (Remote Sensing Applications: Society and Environment, 2024)

Photo/electro catalytic green hydrogen production promoted by Ga modified Co0.6Cu0.4Fe2O4 nano catalysts - Pinki Kotwal; Rohit Jasrotia; Anant Vidya Nidhi; Jahangeer Ahmed; Sanchit Thakur; Abhishek Kandwal; Mohd Fazil; Saad M. Alshehri; Tokeer Ahmad; Ankit Verma; Naresh Sharma; Rajesh Kumar (Environmental Research, 2024)

Using machine learning to improve the estimate of U.S. background ozone - Farnaz Hosseinpour; Naresh Kumar; Trang Tran; Eladio Knipping (Atmospheric Environment, 2024)

Breeding leafy amaranth (Amaranthus spp.) for white rust resistance - Naresh Ponnam; Meenu Kumari; Sangeetha Ganesan; Satyaprakash Barik; Madhuri Pattanaik; Anil Kumar Adamala; Rao VK; Rupa TR; Varalakshmi B; Gobinda Chandra Acharya (South African Journal of Botany, 2023)

Unique green chromatographic method for the qualitative and quantitative analysis of ketoconazole, its impurities and preservatives from ketoconazole cream formulation: Identification of degradants by Q-ToF LCMS and Robustness by Design of Experiments - Siva Krishna Muchakayala; Naresh Kumar Katari; Kalyan Kumar Saripella; Vishnu Murthy Marisetti; Leela Prasad Kowtharapu (Sustainable Chemistry and Pharmacy, 2023)

Mapping of stress and structure controlled upper crustal anisotropy in Kumaon-Gharwal Himalaya - V. Pavan Kumar; D. Srinagesh; Prantik Mandal; Jyotima Kanaujia; B. Naresh; P. Solomon Raju (Physics of the Earth and Planetary Interiors, 2023)

Tricks and tracks in resource recovery from wastewater using bio-electrochemical systems (BES): A systematic review on recent advancements and future directions - Lavanya Addagada; Mukesh Goel; Muhammad Kashif Shahid; Sundramurthy Venkatesa Prabhu; Sasmita Chand; Naresh Kumar Sahoo; Prangya Ranjan Rout (Journal of Water Process Engineering, 2023)

Prevalence of extended spectrum β-lactam, methicillin, and vancomycin resistant zoonotic bacterial pathogens in milk - Raghu Vishweswaraiah; Divya Sharma; Mehak Mehta; Avinash Jaswal; Kriti Dua; Rashmi Mallappa; Diwas Pradhan; A.S. Mariya Divanshi; Gurjinder Kaur; Naresh Kumar; Anil Kumar Puniya (Food and Humanity, 2023)

Morphological and physiological changes (variation) in colchicine induced tetraploids of spine gourd (Momordica dioica Roxb.) in comparison to their diploid counterparts - Devarchan Nirala; Jitendra Kumar Tiwari; Naresh Kumar Sahu; Santosh Kumar Sinha (Plant Physiology Reports, 2023)

Differential gene expression analysis reveals the fast-growth mechanisms in Melia dubia at different stand ages - K Rajarajan; Shailesh Verma; Sakshi Sahu; A Radhakrishna; Naresh Kumar; E Priyadarshini; AK Handa; A Arunachalam (Molecular Biology Reports, 2023)

Expression of mammalian cell entry genes in clinical isolates of M. tuberculosis and the cell entry potential and immunological reactivity of the Rv0590A protein - Chanchal Kumar; Kamal Shrivastava; Anupriya Singh; Varsha Chauhan; Astha Giri; Shraddha Gupta; Naresh Kumar Sharma; Mridula Bose; Sadhna Sharma; Mandira Varma-Basil (Medical Microbiology and Immunology, 2023)

Muscle Transcriptome Sequencing Revealed Thermal Stress–Responsive Regulatory Genes in Farmed Rohu, Labeo rohita (Hamilton, 1822) - Pokanti Vinay Kumar; Kiran D. Rasal; Arpit Acharya; Diganta Dey; Arvind A. Sonwane; Dhalongsaih Reang; R. Rajeshkannan; Sachin S. Pawar; Nitin P. Kurade; Mukesh P. Bhendarkar; Kishore K. Krishnani; Naresh S. Nagpure; et al. (Marine Biotechnology, 2023)

GIS-Based Flood Susceptibility Mapping of Srinagar District, India Using Weights-of-Evidence (WofE), Frequency Ratio (FR) and Fuzzy Gamma Operator (FGO) - Syed Irtiza Majid; Manish Kumar; Pankaj Kumar; Naresh Kumar Verma (Journal of the Indian Society of Remote Sensing, 2023)

Evaluation of indigenous accessions of wheat for spot blotch resistance at the seedling and adult plant stage - Yaratha Nishith Reddy; Malkhan Singh Gurjar; Tej Pratap Jitendra Kumar; Mahender Singh Saharan; Sundeep Kumar; Mukesh Kumar Khokhar; Naresh Kumar; Rashmi Aggarwal (Indian Phytopathology, 2023)

Application of machine learning (individual vs stacking) models on MERRA-2 data to predict surface PM2.5 concentrations over India - Abisheg Dhandapani; Jawed Iqbal; R. Naresh Kumar (Chemosphere, 2023)

Shear wave crustal velocity structure in the Garhwal-Kumaon Himalaya based on noise cross-correlation of Rayleigh wave - Sanjay K. Verma; Naresh Kumar; Devajit Hazarika; Ajay Paul; Dilip K. Yadav; Sanjit K. Pal (Tectonophysics, 2023)

Climate change and coastal morphodynamics: Interactions on regional scales - Piyali Chowdhury; Naresh Kumar Goud Lakku; Susana Lincoln; Jaya Kumar Seelam; Manasa Ranjan Behera (Science of The Total Environment, 2023)

Region-wise and state-wise synthesis of vehicular emissions in India and their mitigation due to vehicular emissions standards - Sandhiya Lakshmanan; Anupama Upadhayay; Naresh Kumar; Sujit Bhattacharya (Science of The Total Environment, 2023)

Per-and polyfluoroalkyl substances (PFAS) as a health hazard: Current state of knowledge and strategies in environmental settings across Asia and future perspectives - Karuna Singh; Naresh Kumar; Asheesh Kumar Yadav; Rahul Singh; Kapil Kumar (Chemical Engineering Journal, 2023)

An updated earthquake catalogue and seismic regimes in the northwest Himalaya: Seismic periodicity associated with strong earthquakes - Vivek G Babu; Naresh Kumar; S K Verma; S K Pal (Journal of Earth System Science, 2023)

Shear-wave velocity models in and around north-east India by modelling Rayleigh wave group velocity dispersion data - Nongmaithem Menaka Chanu; Naresh Kumar; Vivek G Babu; Sagarika Mukhopadhyay; Amit Kumar (Journal of Earth System Science, 2023)

Photocatalytic degradation of bisphenol A by temperature-sensitive magnetic hydrogel with enhanced service life - Wenhui Chen; Wei Mao; Zhiqiang Liu; Weilin Hou; Naresh Kumar; Jun Sun; Xingwei Cai; Cheng Huang; Wei Shen; Fu Yang; Yanjuan Cui; Hian Kee Lee; et al. (Journal of Hazardous Materials, 2023)

Satellite Epidemic of Covid-19 Associated Mucormycosis in India: A Multi-Site Observational Study - Aanchal Satija; Tanu Anand; Aparna Mukherjee; Poonam Sharma Velamuri; Kh. Jitenkumar Singh; Madhuchhanda Das; Kripa Josten; Archana Y. Keche; Nitin M. Nagarkar; Prashant Gupta; D. Himanshu; Sejal N. Mistry; et al. (Mycopathologia, 2023)

Reducing Arsenic Uptake in Cereal Crop Plants with Sugarcane Waste Application: A Comparative Study on the Effects on Physiology, Biochemistry, and Grain Nutrient Status - Ambedkar Gautam; Nikita Basant; Navin Kumar; Kriti; Shiv Naresh Singh; Arvind Kumar Dubey; Gayatri Singh; Babita Kumari; Kavita Shah; Shekhar Mallick (Journal of Plant Growth Regulation, 2023)

Coinfection of porcine astrovirus and other porcine viruses in diarrheic pigs in Haryana, India - Vaishali; Renu Gupta; Mohit Kumar; Nitish Bansal; Vivek; Parveen Kumar; Pawan Kumar; Naresh Jindal (Archives of Virology, 2023)

DNA protection ability, antihyperglycemic potential and in-vivo toxicity assessment of arrowleaf tearthumb ( Persicaria sagittata L.), a neglected aquatic plant species of Eastern Asia - Chongtham Rajiv; Subhra Saikat Roy; Thangjam Surchandra Singh; K. Tamreihao; Pintubala Kshetri; Haobijam Sanjita Devi; Susheel Kumar Sharma; Asem Kajal Devi; Pangambam Langamba; Heikham Naresh Singh; Chongtham Tania; Chongtham Sonia; et al. (Natural Product Research, 2023)

Host and transmission route of Enterocytozoon hepatopenaei (EHP) between dragonfly and shrimp - Naresh Kumar Dewangan; Jianhu Pang; Caiyuan Zhao; Changzheng Cao; Bin Yin; Shaoping Weng; Jianguo He (Aquaculture, 2023)

Monkeypox viral nucleic acids detected using both DNA and RNA extraction workflows - Mark E. Sharkey; Kristina M. Babler; Bhavarth S. Shukla; Samantha M. Abelson; Bader Alsuliman; Ayaaz Amirali; Samuel Comerford; George S. Grills; Naresh Kumar; Jennifer Laine; Jisue Lee; Walter E. Lamar; et al. (Science of The Total Environment, 2023)

Impact of cropping systems on pedogenic distribution and transformations of micronutrients, plant accumulation and microbial community composition in soils: a review - S. S. Dhaliwal; Raj Gupta; A. K. Singh; R. K. Naresh; Agniva Mandal; U. P. Singh; Yogesh Kumar; S. K. Tomar; N. C. Mahajan (Tropical Ecology, 2023)

Characterization of Foot-and-Mouth Disease Virus Serotype O-Specific Single Domain Antibody Expressed in the pET Expression System - Vijay Kumar; Swati Dahiya; Savita Budania; Akhil Kumar Gupta; Punesh Sangwan; Anshul Lather; Pawan Kumar; Naresh Kumar Kakker; Ajit Singh (Indian Journal of Microbiology, 2023)

Melanin biopolymers from microbial world with future perspectives—a review - Helan Soundra Rani Michael; Shri Ranjani Subiramanian; Divyavaahini Thyagarajan; Nazneen Bobby Mohammed; Venkatesh Kumar Saravanakumar; Mageswari Govindaraj; Kalpanadevi Murugasamy Maheswari; Naresh Karthikeyan; Charu Ramesh Kumar (Archives of Microbiology, 2023)

First Molecular Confirmed Outbreak of Malignant Ovine Theileriosis in Sheep from North India - Pallavi Moudgil; Kushal Grakh; Ramesh Kumar; Maneesh Sharma; Renu Gupta; Naresh Jindal (Acta Parasitologica, 2023)

Valorisation of pineapple peel waste as natural surimi gel enhancer and its optimization in Nile tilapia (Oreochromis niloticus) surimi gels - Sanjeev Sharma; Ranendra Kumar Majumdar; Naresh Kumar Mehta (Environmental Science and Pollution Research, 2023)

Dereplication approach for the first time isolation of tatarinowin a and pentadecanoic acid from Acorus calamus L. by using GC-MS - Chetan Kumar; Sabiyah Akhter; Naresh Kumar Satti; Vivek Kumar Gupta; Siya Ram Meena; Ram Vishwakarma; Qazi Parvaiz Hassan; Mahendra Kumar Verma (Natural Product Research, 2023)

Pharmaceutical waste-water treatment via advanced oxidation based integrated processes: An engineering and economic perspective - Amit K. Thakur; Rahul Kumar; Ashutosh Kumar; Ravi Shankar; Nadeem A. Khan; Kaushal Naresh Gupta; Mahendra Ram; Raj Kumar Arya (Journal of Water Process Engineering, 2023)

Magnetically recoverable sol-gel auto-combustion developed Ni1-xCuxDyyFe2-yO4 magnetic nanoparticles for photocatalytic, electrocatalytic, and antibacterial applications - Pinki Kotwal; Rohit Jasrotia; Jyoti Prakash; Jahangeer Ahmed; Ankit Verma; Ritesh Verma; Abhishek Kandwal; Sachin Kumar Godara; Swati Kumari; Pradip K. Maji; Mohd Fazil; Tokeer Ahmad; et al. (Environmental Research, 2023)

Breeding for root-knot nematode resistance in fruiting Solanaceous vegetable crops: a review - Pranaya Pradhan; Ponnam Naresh; Satyaprakash Barik; Gobinda Chandra Acharya; Ramakrushna Bastia; Anil Kumar Adamala; Mahendra Prasad Das (Euphytica, 2023)

Assessment of Bacterial wilt-resistant Solanum genetic resources as rootstocks for yield and fruit quality traits in eggplant - Satyaprakash Barik; Naresh Ponnam; Gobinda Chandra Acharya; Meenu Kumari; Anil Kumar Adamala; Srinivas Petikam; Sangeetha G; Singh TH; Singh HS; Gouri Shankar Sahu (Australasian Plant Pathology, 2023)

Mesoscale eddies with anomalous sea surface temperature and its relation with atmospheric convection over the North Indian Ocean - Venkata Sai Gulakaram; Naresh Krishna Vissa; Prasad Kumar Bhaskaran (International Journal of Climatology, 2023)
Mesoscale eddies are the important phenomenon of world oceans that play a prominent role in influencing the near‐surface atmosphere and transport of heat. Ocean and atmosphere responses due to the presence of oceanic mesoscale eddies are not well studied in the Northern Indian Ocean (NIO) region. The present study analysed the ocean and atmospheric response due to the presence of mesoscale eddies using a composite analysis. Generally, it is assumed that the anti‐cyclonic eddies are associated with the positive anomalies of sea surface temperature (SST), and cyclonic eddies are accompanied by negative anomalies. However, for the two marginal seas in the NIO, that is, the Bay of Bengal (BoB) and Arabian Sea (AS), the composite picture of SST anomalies associated with mesoscale eddies showed an abnormal response of SST. This unusual behaviour of cold SST near anti‐cyclonic eddies and warm SST near cyclonic eddies in BoB and AS is analysed with the mean composites of precipitation, outgoing longwave radiation (OLR), and turbulent fluxes. The mean composites over all anti‐cyclonic eddies reveal the presence of enhanced precipitation and convection (low OLR), whereas over cyclonic eddies, suppressed convection and negative precipitation anomalies are evident. The composites of latent heat flux (LHF), precipitation and OLR near surface cold anti‐cyclonic eddies indicate the loss of heat from the ocean to the atmosphere, intense precipitation along with cloudy conditions are responsible for the cooling of the ocean. Along with this, stronger winds are also evident during cloudy conditions could play a role in anomalous cooling of SST observed near anti‐cyclonic through intense surface mixing. Similarly, vice versa is observed near the surface warm cyclonic eddies. The overlying atmosphere and abnormal response of SST near oceanic eddies are essential for understanding the significant role of oceanic mesoscale eddies in influencing the large‐scale circulation of the atmosphere and climate.

Estimation of income and price elasticities of Indian electricity demand - Nhan Dang Tran; Naresh Chandra Sahu; Pushp Kumar (The Electricity Journal, 2023)

QbD green analytical procedure for Novel study of a genotoxic and carcinogenic compound trace determination in physiological solution compatibility - Leela Prasad Kowtharapu; Naresh Kumar Katari; Siva Krishna Muchakayala; Surya Prakash Rao Pydimarry; Vijay Kumar Rekulapally; Christian A. Sandoval (Sustainable Chemistry and Pharmacy, 2023)

Co-treatment of stabilized landfill leachate and municipal wastewater in a granular activated carbon-sequencing batch reactor (GAC-SBR) - Mohini Verma; Shubhrasekhar Chakraborty; Shweta Kumari; Aalok Gupta; Dewanshu Kumar; Jawed Iqbal; J. Rajesh Banu; Arulazhagan Pugazhendi; R. Naresh Kumar (Process Safety and Environmental Protection, 2023)

High temperature interactions between coal ash and MgO-based refractories in lime kiln conditions - Naresh Kumar Wagri; Markus Carlborg; Matias Eriksson; Charlie Ma; Markus Broström; Britt M. Andersson (Fuel, 2023)

Impact of potential flood on riverbanks in extreme hydro-climatic events, NW Himalaya - Yaspal Sundriyal; Vipin Kumar; Firoz Khan; Mohit Kumar Puniya; Sameeksha Kaushik; Neha Chauhan; Dhirendra Singh Bagri; Naresh Rana (Bulletin of Engineering Geology and the Environment, 2023)

Characterization of fine particulate matter water-soluble inorganic ions and estimation of aerosol acidity at three COALESCE network sites — Mysuru, Bhopal, and Mesra — in India - Abisheg Dhandapani; Jawed Iqbal; Radhakrishnan Naresh Kumar; Ankur Bhardwaj; Deeksha Shukla; Ramya Sunder Raman; Sanyasihally Vasanthkumar Laxmi Prasad; Boohalli Mahadevappa Sadashiva Murthy (Environmental Science and Pollution Research, 2023)

Pollution characteristics and ecological risks of trace elements in PM2.5 over three COALESCE network sites - Bhopal, Mesra, and Mysuru, India - Diksha Haswani; Ramya Sunder Raman; Kajal Yadav; Abisheg Dhandapani; Jawed Iqbal; R. Naresh Kumar; S.V. Laxmi Prasad; Adi Yogesh; Sadashiva Murthy B.M.; K.S. Lokesh (Chemosphere, 2023)

Investigating sensitivity of ozone to emission reductions in the New York City (NYC) metropolitan and downwind areas - Trang Tran; Naresh Kumar; Eladio Knipping (Atmospheric Environment, 2023)

Molecular mechanisms underpinning the silicon-selenium (Si-Se) interactome and cross-talk in stress-induced plant responses - Bhuvnesh Kapoor; Pankaj Kumar; Navjot Singh Gill; Rajnish Sharma; Naresh Thakur; Mohammad Irfan (Plant and Soil, 2023)

Anti-cancer potential of substituted “amino-alkyl-rhodamine” derivatives against MCF-7 human breast cancer cell line - Padma Charan Behera; Varnita Karmakar; Arya Ghosh; Suddhasatya Dey; Naresh Kumar Rangra; Bamaprasad Bag (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effective PFAS degradation by electrochemical oxidation methods-recent progress and requirement - Maryam Mirabediny; Jun Sun; Tsz Tin Yu; Björn Åkermark; Biswanath Das; Naresh Kumar (Chemosphere, 2023)

Degradation rates influence the ability of composite samples to represent 24-hourly means of SARS-CoV-2 and other microbiological target measures in wastewater - Kristina M. Babler; Mark E. Sharkey; Samantha Abelson; Ayaaz Amirali; Aymara Benitez; Gabriella A. Cosculluela; George S. Grills; Naresh Kumar; Jennifer Laine; Walter Lamar; Erik D. Lamm; Jiangnan Lyu; et al. (Science of The Total Environment, 2023)

Type 2 abomasal ulceration in cattle and buffalo: energy and lipid metabolic status, clinico-biochemical parameters, treatment, and prognostic indicators - Syed Ashaq Hussain; Sanjeev Kumar Uppal; Naresh Kumar Sood; Jitender Mohindroo (Tropical Animal Health and Production, 2023)

Techniques to preprocess the climate projections—a review - Shweta Panjwani; S. Naresh Kumar (Theoretical and Applied Climatology, 2023)

Investigating the Biochemical Responses in Wheat Cultivars Exposed to Thermal Power Plant Emission - Yogesh Kumar; Usha Mina; Vishnu D. Rajput; Tatiana Minkina; Soora Naresh Kumar; Ramesh Chandra Harit; Manoj Chandra Garg (Bulletin of Environmental Contamination and Toxicology, 2023)

Impact of tillage cum crop establishment methods and nutrient management strategies on wet rice (Oryza sativa L): crop productivity, water footprint, soil health and profitability in typic Ustochrept soils under semi-arid sub-tropical environment - Mandapelli Sharath Chandra; R. K. Naresh; Rajan Bhatt; Manisha; Papita H. Gourkhede; Rahul Kumar; Praveen V. Kadam; Sandeep Gawdiya (Paddy and Water Environment, 2023)

RETRACTED ARTICLE: Income, coal consumption, and the environmental Kuznets curve in Vietnam - Nhan Dang Tran; Naresh Chandra Sahu; Pushp Kumar (Environmental Science and Pollution Research, 2023)

Tectonic evolution of the neoproterozoic tusham ring complex, Northwestern India: Constraints from geochemistry and zircon U Pb geochronology, and implications for Rodinia supercontinent history - A. Krishnakanta Singh; Naveen Kumar; Sun-Lin Chung; Hao-Yang Lee; M. Santosh; Radhika Sharma; Naresh Kumar; R.K. Bikramaditya; Govind Oinam; Nongmaithem Lakhan (Lithos, 2023)

Paper-based dots and smartphone for detecting counterfeit country eggs - Rohitraj Ray; Ayush Goyal; Anusha Prabhu; Saumya Parekkh; Srinivasulu Maddasani; Naresh Kumar Mani (Food Chemistry, 2023)

Evolution and mitigation of vehicular emissions due to India's Bharat Stage Emission Standards – A case study from Delhi - Madhur D. Gajbhiye; Sandhiya Lakshmanan; Ranjana Aggarwal; Naresh Kumar; Sujit Bhattacharya (Environmental Development, 2023)

Imprint of Diurnal and Semidiurnal Cyclicity in Radon Time Series of MPGO, Ghuttu Garhwal Himalaya: Evidence Based on Singular Spectrum Analysis - Amrita Yadav; Naresh Kumar; S. K. Verma; Vaishali Shukla; Vishal Chauhan (Pure and Applied Geophysics, 2023)

Waste-Derived Fuels and Renewable Chemicals for Bioeconomy Promotion: A Sustainable Approach - Vivek Narisetty; Reshmy R.; Shraddha Maitra; Ayon Tarafdar; Maria Paul Alphy; A. Naresh Kumar; Aravind Madhavan; Ranjna Sirohi; Mukesh Kumar Awasthi; Raveendran Sindhu; Sunita Varjani; Parameswaran Binod (BioEnergy Research, 2023)

Recent Advancements in Microalgal Mediated Valorisation of Wastewater from Hydrothermal Liquefaction of Biomass - Prangya Ranjan Rout; Mukesh Goel; Anee Mohanty; Daya Shankar Pandey; Nirmalya Halder; Sanjay Mukherjee; Shashi Kant Bhatia; Naresh Kumar Sahoo; Sunita Varjani (BioEnergy Research, 2023)

Wastewater generation and treatment by various eco-friendly technologies: Possible health hazards and further reuse for environmental safety - Bhanu Pratap; Saroj Kumar; Sampurna Nand; Iqbal Azad; Ram Naresh Bharagava; Luiz Fernando Romanholo Ferreira; Venkatesh Dutta (Chemosphere, 2023)

Effectiveness of India’s Bharat Stage mitigation measures in reducing vehicular emissions - Madhur D. Gajbhiye; Sandhiya Lakshmanan; Naresh Kumar; Sujit Bhattacharya; Shivnarayan Nishad (Transportation Research Part D: Transport and Environment, 2023)

Electrochemical-based approaches for the treatment of forever chemicals: Removal of perfluoroalkyl and polyfluoroalkyl substances (PFAS) from wastewater - K. Sivagami; Pranshu Sharma; Ansaf V. Karim; Gunda Mohanakrishna; S. Karthika; G. Divyapriya; R. Saravanathamizhan; A. Naresh Kumar (Science of The Total Environment, 2023)

Automatic lithology modelling of coal beds using the joint interpretation of principal component analysis (PCA) and continuous wavelet transform (CWT) - Thinesh Kumar; Seelam Naresh Kumar; G Srinivasa Rao (Journal of Earth System Science, 2023)

Predicting COVID-19 cases using SARS-CoV-2 RNA in air, surface swab and wastewater samples - Helena M. Solo-Gabriele; Shelja Kumar; Samantha Abelson; Johnathon Penso; Julio Contreras; Kristina M. Babler; Mark E. Sharkey; Alejandro M.A. Mantero; Walter E. Lamar; John J. Tallon; Erin Kobetz; Natasha Schaefer Solle; et al. (Science of The Total Environment, 2023)

Ultra-fast and low-cost electroactive biochar production for electroactive-constructed wetland applications: A circular concept for plant biomass utilization - Yamini Mittal; Pratiksha Srivastava; Naresh Kumar; Manish Kumar; Saroj Kumar Singh; Fernando Martinez; Asheesh Kumar Yadav (Chemical Engineering Journal, 2023)

Physiochemical parameters of Apis cerana indica honey as an indicator of bee nutritional status in an anthropogenically managed urban habitat - Vinutha R. Bhatta; Naresh Kumar A (International Journal of Tropical Insect Science, 2022)

Molecular investigations on outbreaks of ovine theileriosis among sheep and goats in Haryana, India - Ramesh Kumar; Pallavi Moudgil; Renu Gupta; Punit Jhandai; Maneesh Sharma; Naresh Jindal (Tropical Animal Health and Production, 2022)

Screening of Capsicum germplasm and inheritance of resistance to chilli leaf curl virus - Rajeev Kumar Yadav; Krishna M. Reddy; K. V. Ashwathappa; Manish Kumar; P. Naresh; Madhavi K. Reddy (Indian Phytopathology, 2022)

Carbon dissipation from surgical cotton production wastewater using macroalgae, microalgae, and activated sludge microbes - Arun Robin Babu; Naresh Kumar Sharma; Matheswaran Manickam (Environmental Science and Pollution Research, 2022)

Growth kinetics, improved plant growth and alleviation of water stress in tomato by water stress tolerant bacteria - K. Tamreihao; Asem Kajal DevI; Pangamba Langamba; Heikham Naresh Singh; Thangjam Surchandra Singh; Chongtham Rajiv; Pintubala Kshetri; B. U. Choudhury; Susheel Kumar Sharma; Subhra Saikat Roy (Antonie van Leeuwenhoek, 2022)

An empirical model-based framework for operational monitoring and prediction of heatwaves based on temperature data - Neetin Narkhede; Rajib Chattopadhyay; S. Lekshmi; Pulak Guhathakurta; Naresh Kumar; M. Mohapatra (Modeling Earth Systems and Environment, 2022)

Epidemiology, clinical features, and molecular detection of orf virus in Haryana (India) and its adjoining areas - Ramesh Kumar; Pallavi Moudgil; Kushal Grakh; Naresh Jindal; Maneesh Sharma; Renu Gupta (Tropical Animal Health and Production, 2022)

Molecular genetic and taxonomical relationship among selected Setaria species using inter simple sequence repeat (ISSR’s) and microsatellite (SSRs) markers - Ramesh Palakurthi; Yugandhar Poli; Vijaya Naresh Juturu; Mallikarjuna Gunti; Sunil Kumar Buchanapalli; Chandra Obul Reddy Puli; Madhusudhana Reddy Araveeti; Chandra Mohan Reddy Chagam Venkata; Chandra Sekhar Akila (Genetic Resources and Crop Evolution, 2022)

Land Use Effect on Soil Organic Carbon Stocks, Microbial Biomass and Basal Respiration in Bundelkhand Region of Central India - Nongmaithem Raju Singh; Dhiraj Kumar; A. K. Handa; Ram Newaj; Mahendra Prasad; Kamini; Naresh Kumar; Asha Ram; Inder Dev; B. P. Bhatt; O. P. Chaturvedi; A. Arunachalam; et al. (Agricultural Research, 2022)

Sub-lineages of Taenia solium Asian Genotype Recorded in North India - Pallavi Moudgil; Ramesh Kumar; Naresh Jindal; Aman D. Moudgil (Acta Parasitologica, 2022)

Serum glucose-regulated protein 78 (GRP78) levels in COVID-19-associated mucormycosis: results of a case–control study - Valliappan Muthu; Manpreet Dhaliwal; Arunima Sharma; Divya Nair; H. Mohan Kumar; Shivaprakash M. Rudramurthy; Inderpaul Singh Sehgal; Hansraj Choudhary; Naresh Panda; Arunaloke Chakrabarti; Ritesh Agarwal (Mycopathologia, 2022)

Efficacy of Arbuscular Mycorrhizal Fungi and Bacterial Inoculants in Enhancing Yield of Phaseolus mungo L. and Vigna radiata (L.) R. Wilczek under Central Indian Conditions - Ashok Shukla; Anil Kumar; Rajendra Prasad; Naresh Kumar; S. K. Dhyani; O. P. Chaturvedi; Ayyanadar Arunachalam (Journal of Soil Science and Plant Nutrition, 2022)

Identification and validation of simple sequence repeats markers in Tilletia indica and compatibility assay of monosporidial lines - Malkhan Singh Gurjar; Prachi Jain; Shekhar Jain; Naresh Kumar; Mahender Singh Saharan; Rashmi Aggarwal (Indian Phytopathology, 2022)

Co-metabolic biodegradation of 4-bromophenol in a mixture of pollutants system by Arthrobacter chlorophenolicus A6 - Mitali Madhusmita Sahoo; Naresh Kumar Sahoo; Achlesh Daverey; Sangeeta Raut (Ecotoxicology, 2022)

Hydro-geochemical analysis based on entropy and geostatistics model for delineation of anthropogenic ground water pollution for health risks assessment of Dhenkanal district, India - Manas Ranjan Naik; Manas Barik; K. V. Prasad; Ajay Kumar; Akshaya Kumar Verma; Sunil Kumar Sahoo; Vivekanand Jha; Naresh Kumar Sahoo (Ecotoxicology, 2022)

Development and characterization of a new gill cell line from the striped catfish, Pangasianodon hypophthalmus (Sauvage, 1878) - Arjunan Sathiyanarayanan; Mukunda Goswami; Naresh Nagpure; Gireesh Babu P; Dhanjit Kumar Das (Fish Physiology and Biochemistry, 2022)

Silicon triggers the signalling molecules and stress-associated genes for alleviating the adverse effect of terminal heat stress in wheat with improved grain quality - Ranjeet Ranjan Kumar; Sumedha Ahuja; Gyanendra K. Rai; Sudhir Kumar; Dwijesh Mishra; Soora Naresh Kumar; Anil Rai; Bhupinder Singh; Viswanathan Chinnusamy; Shelly Praveen (Acta Physiologiae Plantarum, 2022)

Machine learning-based modeling to predict inhibitors of acetylcholinesterase - Hardeep Sandhu; Rajaram Naresh Kumar; Prabha Garg (Molecular Diversity, 2022)

Impact of agricultural management practices on soil carbon sequestration and its monitoring through simulation models and remote sensing techniques: A review - Agniva Mandal; Atin Majumder; S. S. Dhaliwal; A. S. Toor; Pabitra Kumar Mani; R. K. Naresh; Raj K. Gupta; Tarik Mitran (Critical Reviews in Environmental Science and Technology, 2022)

Recent biotechnological trends in lactic acid bacterial fermentation for food processing industries - Tirath Raj; K. Chandrasekhar; A. Naresh Kumar; Sang-Hyoun Kim (Systems Microbiology and Biomanufacturing, 2022)

Design and synthesis of hybrid nanostructures for sustainable energy and environmental remediation - Naresh A. Rajpurohit; Kaushalya Bhakar; Meena Nemiwal; Dinesh Kumar (Arabian Journal of Geosciences, 2022)

Evaluation of heavy rainfall warnings of India National Weather Forecasting Service for monsoon season (2002–2018) - M Mohapatra; Naresh Kumar; Krishna Mishra; Sunitha Devi (Journal of Earth System Science, 2021)

A study of Palnadu earthquake sequence in the Cuddapah basin and its tectonic implications - D Srinagesh; T C Sunilkumar; B Naresh; S Vitthal; Dhiraj K Singh; Ravi P Singh; Mahalaxmi Naidu; G Suresh; P Solomon Raju; V Pavan Kumar; Prantik Mandal; A N S Sarma (Journal of Earth System Science, 2021)

Monsoonal rainfall induced shallow earthquake Swarm in the Amravati district of the central India - Monika Wadhawan; Naresh Rana; Vineet Gahalaut; Manjeet Singh; Kulbir Singh; G Suresh; O P Mishra; Akshay Kumar Joshi; A V Kulkarni; Mahendra Singh; A K Das (Journal of Earth System Science, 2021)

Geochemical characteristics of fluorine- and chlorine-bearing biotite from Tusham Ring Complex, NW India: Constraints on halogen distribution and geodynamic evolution - Naveen Kumar; Naresh Kumar; Radhika Sharma; A Krishnakanta Singh (Journal of Earth System Science, 2021)

A strategy to decrease vectorial competence of dengue mosquito Aedes aegypti by alteration of its gut microbiota using Indian traditional medicinal plants - Kamal Kumar Gupta; Meenakshi Prejneshu; Mohit Aggarwal; Chetkar Chandra Keshvam; Vinay Kumar Dubey; Manish Kumar Mishra; Naresh Singh (International Journal of Tropical Insect Science, 2021)

Occurrence of Dirofilaria immitis in Stray Dogs from Nepal - Subash Rimal; Anil Adhikari; Rabin Acharya; Dinesh Kumar Singh; Naresh Prasad Joshi; Birendra Shrestha; Krishna Kaphle; Khaled Mohamed El-Dakhly; Alessio Giannelli (Acta Parasitologica, 2021)

Infectious spleen and kidney necrosis virus‐associated large‐scale mortality in farmed giant gourami, Osphronemus goramy, in India - Thangaraj Raja Swaminathan; Nithianantham Sundar Raj; Prasannan Geetha Preena; Pravata Kumar Pradhan; Neeraj Sood; Rahul Girish Kumar; Arun Sudhagar; Naresh Kumar Sood (Journal of Fish Diseases, 2021)
Megalocytivirus cause diseases that have serious economic impacts on aquaculture, mainly in East and South‐East Asia. Five primary genotypes are known: infectious spleen and kidney necrosis virus (ISKNV), red sea bream iridovirus (RSIV), turbot reddish body iridovirus (TRBIV), threespine stickleback iridovirus (TSIV) and scale drop disease virus (SDDV). ISKNV‐mediated infectious spleen and kidney necrosis disease (ISKND) is a major viral disease in both freshwater and marine fish species. In this study, we report the isolation of ISKNV from diseased giant gourami, Osphronemus goramy, in India. Transmission electron microscopy of ultrathin sections of kidney and spleen revealed the presence of numerous polygonal naked viral particles having an outer nucleocapsid layer within the cytoplasm of enlarged cells (115–125 nm). Molecular and phylogenetic analyses confirmed the presence of ISKNV and the major capsid protein (MCP) (1,362 bp) gene in the infected fish had a high similarity to the other ISKNV‐I isolates. Moreover, ISKNV was propagated in the Astronotus ocellatus fin (AOF) cell line and further confirmed genotypically. A high mortality rate (60%) was observed in gourami fish injected with ISKNV‐positive tissue homogenate through challenge studies. Considering the lethal nature of ISKNV, the present study spotlights the implementation of stringent biosecurity practices for the proper control of the disease in the country.

Implications of Site Effects and Attenuation Properties for Estimation of Earthquake Source Characteristics in Kinnaur Himalaya, India - Richa Kumari; Parveen Kumar; Naresh Kumar; Sandeep (Pure and Applied Geophysics, 2021)

Augmented sequence features and subcellular localization for functional characterization of unknown protein sequences - Saurabh Agrawal; Dilip Singh Sisodia; Naresh Kumar Nagwani (Medical & Biological Engineering & Computing, 2021)

Do energy consumption and environmental quality enhance subjective wellbeing in G20 countries? - Neha Kumari; Pushp Kumar; Naresh Chandra Sahu (Environmental Science and Pollution Research, 2021)

Bioelectrochemical system-mediated waste valorization - K. Chandrasekhar; A. Naresh Kumar; Tirath Raj; Gopalakrishnan Kumar; Sang-Hyoun Kim (Systems Microbiology and Biomanufacturing, 2021)
Bioelectrochemical systems (BESs) are a new and emerging technology in the field of fermentation technology. Electrical energy was provided externally to the microbial electrolysis cells (MECs) to generate hydrogen or value-added chemicals, including caustic, formic acid, acetic acid, and peroxide. Also, BES was designed to recover nutrients, metals or remove recalcitrant compounds. The variety of naturally existing microorganisms and enzymes act as a biocatalyst to induce potential differences amid the electrodes. BESs can be performed with non-catalyzed electrodes (both anode and cathode) under favorable circumstances, unlike conventional fuel cells. In recent years, value-added chemical producing microbial electrosynthesis (MES) technology has intensely broadened the prospect for BES. An additional strategy includes the introduction of innovative technologies that help with the manufacturing of alternative materials for electrode preparation, ion-exchange membranes, and pioneering designs. Because of this, BES is emerging as a promising technology. This article deliberates recent signs of progress in BESs so far, focusing on their diverse applications beyond electricity generation and resulting performance.

Impact of climate change on cereal production: evidence from lower-middle-income countries - Pushp Kumar; Naresh Chandra Sahu; Siddharth Kumar; Mohd Arshad Ansari (Environmental Science and Pollution Research, 2021)

Molecular detection and characterization reveals circulation of multiple genotypes of porcine astrovirus in Haryana, India - Rajpreet Kour; Parveen Kumar; Naresh Jindal; Sanjeevna Kumari Minhas; Ramesh Kumar; Akhil Kumar Gupta; Anu Malik (Archives of Virology, 2021)

Spatial and temporal variation in daily precipitation indices over Western Himalayas - Naresh Kumar; M Mohapatra; A P Dimri; M Anand (Journal of Earth System Science, 2021)

Characterization of earthquake hazard at the Palghar and Pulichintala swarm activity regions (India) through three-dimensional modelling of b-value and fractal (correlation) dimensions - Prantik Mandal; D. Srinagesh; G. Suresh; B. Naresh; Mahalaxmi Naidu; Dhiraj Kumar Singh; K. Swathi; Arti Devi; S. Vittal; P. K. Vengala; R. Vijaya Raghavan; M. Shekar; et al. (Natural Hazards, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Mapping and Electronic Publishing of Shoreline Changes using UAV Remote Sensing and GIS - N. Shenbagaraj; K. Senthil kumar; A. Mohamed Rasheed; J. Leostalin; M. Naresh Kumar (Journal of the Indian Society of Remote Sensing, 2021)

Irrigation scheduling and requirements of processing tomato (Lycopersicon esculentum L.) in Eastern Canada - Chandra A. Madramootoo; Felix Jaria; Naresh Kumar Arumugagounder Thangaraju (Irrigation Science, 2021)

Evaluation of elite bread wheat lines for resistance to blast disease in Bangladesh - Krishna Kanta Roy; Md Mostofa Ali Reza; Md Muzahid-E-Rahman; Md Babul Anwar; Kishowar-E-Mustarin; Muhammad Rezaul Kabir; Paritosh Kumar Malaker; Naresh Chandra Deb Barma; Md Israil Hossain; Xinyao He; Aakash Chawade; Pawan Kumar Singh (Euphytica, 2021)

Possible Biomarkers and Contributing Factors of Psychosis: a Review - Monu Yadav; Naresh Kumar; Anil Kumar; Deepak Kumar Jindal; Mini Dahiya (Current Pharmacology Reports, 2021)

Influence of the water–sediment interaction on the major ions chemistry and fluoride pollution in groundwater of the Older Alluvial Plains of Delhi, India - Shakir Ali; Shashank Shekhar; Trupti Chandrasekhar; Akhilesh Kumar Yadav; Naresh Kumar Arora; Chandrashekhar Azad Kashyap; Prosun Bhattacharya; S P Rai; Prabhas Pande; Dornadulla Chandrasekharam (Journal of Earth System Science, 2021)

Analysis of mitochondrial recombination in the male sterile Brassica juncea cybrid Og1 and identification of the molecular basis of fertility reversion - Naresh Vasupalli; Vajinder Kumar; Ramcharan Bhattacharya; Shripad R. Bhat (Plant Molecular Biology, 2021)

Xanthene‐based Fluorescence Turn‐on Probe for Highly Acidic pH Range in Aqueous Solution - Bhanu Priya; Vibha Mahajan; Naresh Kumar; Roopa (Journal of Fluorescence, 2021)

First report of barley blast caused by Magnaporthe oryzae pathotype Triticum (MoT) in Bangladesh - Krishna Kanta Roy; Md Mostofa Ali Reza; Md Muzahid-E-Rahman; Kishowar E. Mustarin; Paritosh Kumar Malaker; Naresh Chandra Deb Barma; Xinyao He; Pawan Kumar Singh (Journal of General Plant Pathology, 2021)

Effect of ethanol and cocaine on [11C]MPC-6827 uptake in SH-SY5Y cells - Naresh Damuka; Miranda Orr; Paul W. Czoty; Jeffrey L. Weiner; Thomas J. Martin; Michael A. Nader; Avinash H. Bansode; Buddhika S. Liyana Pathirannahel; Akiva Mintz; Shannon L. Macauley; Suzanne Craft; Kiran Kumar Solingapuram Sai (Molecular Biology Reports, 2021)
Microtubules (MTs) are structural units in the cytoskeleton. In brain cells they are responsible for axonal transport, information processing, and signaling mechanisms. Proper function of these processes is critical for healthy brain functions. Alcohol and substance use disorders (AUD/SUDs) affects the function and organization of MTs in the brain, making them a potential neuroimaging marker to study the resulting impairment of overall neurobehavioral and cognitive processes. Our lab reported the first brain-penetrant MT-tracking Positron Emission Tomography (PET) ligand [ 11 C]MPC-6827 and demonstrated its in vivo utility in rodents and non-human primates. To further explore the in vivo imaging potential of [ 11 C]MPC-6827, we need to investigate its mechanism of action. Here, we report preliminary in vitro binding results in SH-SY5Y neuroblastoma cells exposed to ethanol (EtOH) or cocaine in combination with multiple agents that alter MT stability. EtOH and cocaine treatments increased MT stability and decreased free tubulin monomers. Our initial cell-binding assay demonstrated that [ 11 C]MPC-6827 may have high affinity to free/unbound tubulin units. Consistent with this mechanism of action, we observed lower [ 11 C]MPC-6827 uptake in SH-SY5Y cells after EtOH and cocaine treatments (e.g., fewer free tubulin units). We are currently performing in vivo PET imaging and ex vivo biodistribution studies in rodent and nonhuman primate models of AUD and SUDs and Alzheimer's disease.

Deciphering pollution vulnerability zones of River Yamuna in relation to existing land use land cover in Panipat, Haryana, India - Lakhvinder Kaur; Madhuri S. Rishi; Naresh Kumar Arora (Environmental Monitoring and Assessment, 2021)

Evaluation of Europium Biosorption Using Deinococcus radiodurans - Ananya Jena; Sanghamitra Pradhan; Sujata Mishra; Naresh Kumar Sahoo (Environmental Processes, 2021)

Variability of durum wheat genotypes in terms of physio-biochemical traits against salinity stress - Shobha Soni; Ashwani Kumar; Nirmala Sehrawat; Naresh Kumar; Gurpreet Kaur; Arvind Kumar; Anita Mann (Cereal Research Communications, 2021)

Effect of Repeated Freezing-Thawing on Protein Fractions, Textural, and Functional Properties of Few Species of Freshwater Fishes (Indian Major Carps) - Swapnarani Samantaray; Naresh Kumar Mehta; Banalata Rout; R. K. Majumdar; Sanjeev Sharma; Ankeeta Nayak; Prasenjit Pal (Journal of Aquatic Food Product Technology, 2021)

Antiradical Properties of trans-2-(4-substituted-styryl)-thiophene - Anamika Gusain; Naresh Kumar; Jagdeep Kumar; Gunjan Pandey; Prasanta Kumar Hota (Journal of Fluorescence, 2021)

Solena amplexicaullis (Lam.) Gandhi: an underutilized cucurbit in India - Meenu Kumari; G. C. Acharya; P. Naresh; P. K. Bhanja; Yogesh Kumar (Genetic Resources and Crop Evolution, 2021)

Metabolic Bone Profile of Healthy Adult North Indian Population from Chandigarh Urban Bone Epidemiological Study (CUBES) - Anshita Aggarwal; Sant Ram; Abhilasha Garg; Rimesh Pal; Anil Bhansali; Priyanka Singh; Sadhna Sharma; J. S. Thakur; Naresh Sachdeva; Sanjay Kumar Bhadada (Indian Journal of Clinical Biochemistry, 2021)

Hydro-geochemical assessment of groundwater through statistical analysis for sustainable usage in Medchal Mandal, Hyderabad, India - D. Naresh Kumar (Sustainable Water Resources Management, 2020)

Role of site effect for the evaluation of attenuation characteristics of P, S and coda waves in Kinnaur region, NW Himalaya - Richa Kumari; Parveen Kumar; Naresh Kumar; Sandeep (Journal of Earth System Science, 2020)

Real-time optimal spatiotemporal sensor placement for monitoring air pollutants - Rajib Mukherjee; Urmila M. Diwekar; Naresh Kumar (Clean Technologies and Environmental Policy, 2020)

Interaction of the surface bound antimicrobial peptides melimine and Mel4 with Staphylococcus aureus - Muhammad Yasir; Debarun Dutta; Naresh Kumar; Mark D. P. Willcox (Biofouling, 2020)

Bamboo-based agroforestry system (Dendrocalamus strictus + sesame–chickpea) for enhancing productivity in semi-arid tropics of central India - Inder Dev; Asha Ram; Sudhir Pal Ahlawat; Dana Ram Palsaniya; Ramesh Singh; Shiv Kumar Dhyani; Naresh Kumar; Rama Kant Tewari; Mahendra Singh; Sridhar K. Babanna; Ram Newaj; Ragunandan Prasad Dwivedi; et al. (Agroforestry Systems, 2020)

Whole Exome Sequencing Identifies a Novel Homozygous Duplication Mutation in the VPS13B Gene in an Indian Family with Cohen Syndrome - Pankhuri Kaushik; Naresh Mahajan; Satish C. Girimaji; Arun Kumar (Journal of Molecular Neuroscience, 2020)

Development and characterization of a new DRCF cell line from Indian wild strain zebrafish Danio rerio (Hamilton 1822) - Lakan Lal Meena; Mukunda Goswami; Aparna Chaudhari; Naresh S. Nagpure; P. Gireesh-Babu; Akhilesh Dubey; Dhanjit Kumar Das (Fish Physiology and Biochemistry, 2020)

Evaluating the impact of climate change in threshold values of thermodynamic indices during pre-monsoon thunderstorm season over Eastern India - Rajesh Kumar Sahu; Jiteshwar Dadich; Bhishma Tyagi; Naresh Krishna Vissa; Jyotsna Singh (Natural Hazards, 2020)

Differential Pulse Polarographic Investigations on Glyphosate and Glufosinate Herbicides in Relation to Their Environmental Analysis - Devender Kumar Sharma; Naresh Kumar; Akhil Chaudhary; Pushap Raj (Bulletin of Environmental Contamination and Toxicology, 2020)

Abatement of enteric methane production from lactating Murrah buffaloes (Bubalus bubalis) with improving production performance and immune status through dietary supplementation of composite feed additive - Kiran Attri; Avijit Dey; Satbir Singh Dahiya; Shyam Sundar Paul; Andonissamy Jerome; Anurag Bharadwaj; Naresh Kumar Kakker (Environmental Science and Pollution Research, 2020)

Evaluation of selected global climate models for extreme temperature events over India - Shweta Panjwani; S. Naresh Kumar; Laxmi Ahuja; Adlul Islam (Theoretical and Applied Climatology, 2020)

Non-invasive biomonitoring of mercury in birds near thermal power plants: lessons from Maharashtra, India - Sunidhi Thakur; Shalini Dhyani; Kavita Bramhanwade; Krishna Kumar Pandey; Naresh Bokade; Ramesh Janipella; Paras Pujari (Environmental Monitoring and Assessment, 2020)

Multifarious Pharmacological Applications of Green Routed Eco-Friendly Iron Nanoparticles Synthesized by Streptomyces Sp. (SRT12) - Srinath Rajeswaran; Somasundaram Somasundaram Thirugnanasambandan; Naresh Kumar Dewangan; Rajesh Kannan Moorthy; Saravanan Kandasamy; Ravikumar Vilwanathan (Biological Trace Element Research, 2020)

Evaluation of a Loop-Mediated Isothermal Amplification Technique for the Rapid Visual Detection of Hepatozoon canis Infection - Manraj Deep Singh; Harkirat Singh; Nirbhay Kumar Singh; Niraj Kumar Singh; Naresh Kumar Sood; Shitanshu Shekar Rath (Acta Parasitologica, 2020)

Molecular characterization of chicken astroviruses in gout-affected commercial broiler chickens in Haryana, India - Sumitra Panigrahi; Naresh Jindal; Pawan Kumar; Sanjay Barua; Naveen Kumar; Thachamvally Riyesh; Yogesh Chander (VirusDisease, 2019)

Occurrence and variability of begomoviruses associated with bhendi yellow vein mosaic and okra enation leaf curl diseases in south-western India - Madhvi Naresh; Zainul Abdeen Khan; Rohit Kumar; Sumit P. Kale; Vijay M. Patil; Jaising C. Rajput; Indranil Dasgupta (VirusDisease, 2019)

Clinical Evaluation of Glycoproteins and Inflammatory Cytokines in the Serum of Dogs Affected with Canine Mammary Cancer - Omer Khalil Baba; Naresh Kumar Sood; Kuldip Gupta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Understanding the relationship between soil properties and litter chemistry in three forest communities in tropical forest ecosystem - Shruti Mishra; Kripal Singh; Nayan Sahu; Shiv Naresh Singh; N. Manika; L. B. Chaudhary; M. K. Jain; Vipin Kumar; Soumit K. Behera (Environmental Monitoring and Assessment, 2019)

Modeling the impact of population density on carbon dioxide emission and its control: effects of greenbelt plantation and seaweed cultivation - Shyam Sundar; Ashish Kumar Mishra; Ram Naresh; J. B. Shukla (Modeling Earth Systems and Environment, 2019)

Buffalo liver transcriptome analysis suggests immune tolerance as its key adaptive mechanism during early postpartum negative energy balance - Sudhakar Singh; Naresh Golla; Davinder Sharma; Dheer Singh; Suneel Kumar Onteru (Functional & Integrative Genomics, 2019)

Prioritization of global climate models using fuzzy analytic hierarchy process and reliability index - Shweta Panjwani; S. Naresh Kumar; Laxmi Ahuja; Adlul Islam (Theoretical and Applied Climatology, 2019)

Regression analysis of aerosol optical properties with long-term MODIS data using forward selection method - Pramod Kumar; Mohit Mann; Naresh Chandra Gupta (Meteorology and Atmospheric Physics, 2019)

Efficacy of a school-based intervention to bring awareness about PCB contamination and exposure avoidance in Guánica, Puerto Rico - Daisy Ramirez-Ortiz; Glenda L. Almodóvar-Morales; Samuel Hopwood; Naresh Kumar (Environmental Science and Pollution Research, 2019)

Localization, distribution and expression of growth hormone in the brain of Asian Catfish, Clarias batrachus - Raj Naresh Gopal; Pankaj Kumar; Bechan Lal (Brain Structure and Function, 2019)

Design, synthesis and biological evaluation of alantolactone derivatives as potential anti-inflammatory agents - Chetan Kumar; Anil Kumar; Yedukondalu Nalli; Waseem I. Lone; Naresh K. Satti; M. K. Verma; Zabeer Ahmed; Asif Ali (Medicinal Chemistry Research, 2019)

A spore-based miniaturized novel assay for rapid aflatoxin detection in milk - Namita Ashish Singh; Naresh Kumar; H. V. Raghu; Sunil Bhand; Sudhir Chandra; Pradeep Kumar Sharma (Environmental Chemistry Letters, 2019)

Design and synthesis of novel 6-substituted quinazoline-2-thiols - Satya Karuna Pulakhandam; Naresh Kumar Katari; Sreekantha B. Jonnalagadda (Molecular Diversity, 2019)

Global wheat production with 1.5 and 2.0°C above pre‐industrial warming - Bing Liu; Pierre Martre; Frank Ewert; John R. Porter; Andy J. Challinor; Christoph Müller; Alex C. Ruane; Katharina Waha; Peter J. Thorburn; Pramod K. Aggarwal; Mukhtar Ahmed; Juraj Balkovič; et al. (Global Change Biology, 2019)
Efforts to limit global warming to below 2°C in relation to the pre‐industrial level are under way, in accordance with the 2015 Paris Agreement. However, most impact research on agriculture to date has focused on impacts of warming >2°C on mean crop yields, and many previous studies did not focus sufficiently on extreme events and yield interannual variability. Here, with the latest climate scenarios from the Half a degree Additional warming, Prognosis and Projected Impacts (HAPPI) project, we evaluated the impacts of the 2015 Paris Agreement range of global warming (1.5 and 2.0°C warming above the pre‐industrial period) on global wheat production and local yield variability. A multi‐crop and multi‐climate model ensemble over a global network of sites developed by the Agricultural Model Intercomparison and Improvement Project (AgMIP) for Wheat was used to represent major rainfed and irrigated wheat cropping systems. Results show that projected global wheat production will change by −2.3% to 7.0% under the 1.5°C scenario and −2.4% to 10.5% under the 2.0°C scenario, compared to a baseline of 1980–2010, when considering changes in local temperature, rainfall, and global atmospheric CO 2 concentration, but no changes in management or wheat cultivars. The projected impact on wheat production varies spatially; a larger increase is projected for temperate high rainfall regions than for moderate hot low rainfall and irrigated regions. Grain yields in warmer regions are more likely to be reduced than in cooler regions. Despite mostly positive impacts on global average grain yields, the frequency of extremely low yields (bottom 5 percentile of baseline distribution) and yield inter‐annual variability will increase under both warming scenarios for some of the hot growing locations, including locations from the second largest global wheat producer—India, which supplies more than 14% of global wheat. The projected global impact of warming

Genetic Structuring in Riverine Population of Channa striata (Bloch, 1793) from India using Cytochrome Oxidase I Gene - Vishwamitra Singh Baisvar; Ravindra Kumar; Mahender Singh; Ajay Kumar Singh; U. K. Chauhan; Naresh Sahebrao Nagpure; Basdeo Kushwaha (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Functional annotation of differentially expressed genes under salt stress in Dichanthium annulatum - Anita Mann; Naresh Kumar; Charu Lata; Ashwani Kumar; Arvind Kumar; B. L. Meena (Plant Physiology Reports, 2019)

Genetic diversity and population structure analysis of Indian garlic (Allium sativum L.) collection using SSR markers - Mukesh Kumar; V. Rakesh Sharma; Vipin Kumar; Ujjawal Sirohi; Veena Chaudhary; Shiveta Sharma; Gautam Saripalli; R. K. Naresh; Hemant Kumar Yadav; Shailendra Sharma (Physiology and Molecular Biology of Plants, 2019)

Coda Q estimation for Kinnaur region and surrounding part of NW Himalaya - Naresh Kumar; Dhirendra Nath Yadav (Journal of Seismology, 2019)

Engine parameter optimization of palm oil biodiesel as alternate fuel in CI engine - Akula Naresh Kumar; Pisipaty Srinivas Kishore; Kalidindi Brahma Raju; Nanthagopal Kasianantham; Ashok Bragadeshwaran (Environmental Science and Pollution Research, 2019)

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Assessment of cortical bone microdamage following insertion of microimplants using optical coherence tomography: a preliminary study - Hemanth Tumkur Lakshmikantha; Naresh Kumar Ravichandran; Mansik Jeon; Jeehyun Kim; Hyo-sang Park (Journal of Zhejiang University-SCIENCE B, 2018)

Multimodel ensembles improve predictions of crop–environment–management interactions - Daniel Wallach; Pierre Martre; Bing Liu; Senthold Asseng; Frank Ewert; Peter J. Thorburn; Martin van Ittersum; Pramod K. Aggarwal; Mukhtar Ahmed; Bruno Basso; Christian Biernath; Davide Cammarano; et al. (Global Change Biology, 2018)
A recent innovation in assessment of climate change impact on agricultural production has been to use crop multimodel ensembles ( MME s). These studies usually find large variability between individual models but that the ensemble mean (e‐mean) and median (e‐median) often seem to predict quite well. However, few studies have specifically been concerned with the predictive quality of those ensemble predictors. We ask what is the predictive quality of e‐mean and e‐median, and how does that depend on the ensemble characteristics. Our empirical results are based on five MME studies applied to wheat, using different data sets but the same 25 crop models. We show that the ensemble predictors have quite high skill and are better than most and sometimes all individual models for most groups of environments and most response variables. Mean squared error of e‐mean decreases monotonically with the size of the ensemble if models are added at random, but has a minimum at usually 2–6 models if best‐fit models are added first. Our theoretical results describe the ensemble using four parameters: average bias, model effect variance, environment effect variance, and interaction variance. We show analytically that mean squared error of prediction ( MSEP ) of e‐mean will always be smaller than MSEP averaged over models and will be less than MSEP of the best model if squared bias is less than the interaction variance. If models are added to the ensemble at random, MSEP of e‐mean will decrease as the inverse of ensemble size, with a minimum equal to squared bias plus interaction variance. This minimum value is not necessarily small, and so it is important to evaluate the predictive quality of e‐mean for each target population of environments. These results provide new information on the advantages of ensemble predictors, but also show their limitations.

Enhancing the Proficiency of Water Use in Wheat Through Nitrogen Forms, Irrigation Intervals and Soil Conditioners - S.M.M. Abdou; R. Ahmed Azza; S. Naresh Kumar; F.R.M. Farrag (Irrigation and Drainage, 2018)
Field experiments were carried out at the Tameia Agricultural Research Station, Fayoum Governorate, Egypt, during the 2013/14 and 2014/15 seasons in order to study the impact of nitrogen fertilization forms, irrigation intervals and some soil conditioners on the yield, yield components and crop water relations of wheat (Giza 168). Two nitrogen forms with three irrigation intervals, i.e. I 1 : irrigation at 14 days, I 2 : 21 days and I 3 : 28 days with soil conditioners at the rate of 11.9 t ha ‐1 , i.e. C 1 control (without any addition), C 2 : compost, C 3 : rice straw and C 4 : sawdust with three replications in a split‐split plot design. Results indicate that the highest wheat grain yields in both years were detected from a combination of applying liquid ammonia gas, irrigation at 14‐day intervals and addition of compost. This treatment also gave higher values for yield components, uptake of nitrogen, phosphorus and potassium and their concentration in the grain. Further, it resulted in highest values for the consumptive use of water as well as water productivity. Thus, a combination of applying liquid ammonia gas, irrigation at 14‐day intervals and addition of compost can be adopted in wider areas in Egypt for enhanced wheat grain yield. © 2018 John Wiley & Sons, Ltd.

Substituent Dependent Optical Properties of p-phenyl Substituted ethenyl-E-thiophenes - Naresh Kumar; Mahalingavelar Paramasivam; Jagdeep Kumar; Anamika Gusain; Prasanta Kumar Hota (Journal of Fluorescence, 2018)

Experimental analysis of performance and emission on DI diesel engine fueled with diesel-palm kernel methyl ester-triacetin blends: a Taguchi fuzzy-based optimization - Jibitesh Kumar Panda; Gadepalli Ravi Kiran Sastry; Ram Naresh Rai (Environmental Science and Pollution Research, 2018)

Characterization and Identification of Recalcitrant Organic Pollutants (ROPs) in Tannery Wastewater and Its Phytotoxicity Evaluation for Environmental Safety - Ram Naresh Bharagava; Gaurav Saxena; Sikandar I. Mulla; Devendra Kumar Patel (Archives of Environmental Contamination and Toxicology, 2018)

Biodegradation and Kinetic Study of 4-Chlorophenol in Bioreactor Packed with Stabilized Bacteria Entrapped in Calcium Alginate Beads System - Naresh Kumar Sahoo; Namita Panigrahy (Environmental Processes, 2018)

Attenuation of Glutamate-Induced Excitotoxicity by Withanolide-A in Neuron-Like Cells: Role for PI3K/Akt/MAPK Signaling Pathway - Nawab John Dar; Naresh Kumar Satti; Prabhu Dutt; Abid Hamid; Muzamil Ahmad (Molecular Neurobiology, 2018)

Modeling the impact of media awareness programs on mitigation of carbon dioxide emitted from automobiles - Shyam Sundar; Ashish Kumar Mishra; Ram Naresh (Modeling Earth Systems and Environment, 2018)

Effect of levofloxacin, pazufloxacin, enrofloxacin, and meloxicam on the immunolocalization of ABCG-2 transporter protein in rabbit retina - Adil Mehraj Khan; Satyavan Rampal; Naresh Kumar Sood (Environmental Science and Pollution Research, 2018)

Effects of open dumping of MSW on metal contamination of soil, plants, and earthworms in Ranchi, Jharkhand, India - Monika Singh; Mohini Verma; R. Naresh Kumar (Environmental Monitoring and Assessment, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Isolation of three new metabolites and intervention of diazomethane led to separation of compound 1 & 2 from an endophytic fungus, Cryptosporiopsis sp. depicting cytotoxic activity - Sunil Kumar; Yedukondalu Nalli; Masroor Qadri; Syed Riyaz-Ul-Hassan; Naresh K. Satti; Vivek Gupta; Shashi Bhushan; Asif Ali (Medicinal Chemistry Research, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Salivary miR-16, miR-191 and miR-223: intuitive indicators of dominant ovarian follicles in buffaloes - Prashant Singh; Naresh Golla; Pankaj Singh; Vijay Simha Baddela; Subhash Chand; Rubina Kumari Baithalu; Dheer Singh; Suneel Kumar Onteru (Molecular Genetics and Genomics, 2017)

Variable anelastic attenuation and site effect in estimating source parameters of various major earthquakes including M w 7.8 Nepal and M w 7.5 Hindu kush earthquake by using far-field strong-motion data - Naresh Kumar; Parveen Kumar; Vishal Chauhan; Devajit Hazarika (International Journal of Earth Sciences, 2017)

Withanone, an Active Constituent from Withania somnifera, Affords Protection Against NMDA-Induced Excitotoxicity in Neuron-Like Cells - Nawab John Dar; Javeed Ahmad Bhat; Naresh Kumar Satti; Parduman Raj Sharma; Abid Hamid; Muzamil Ahmad (Molecular Neurobiology, 2017)

Substituent Dependence Charge Transfer and Photochemical Properties of Donor-Acceptor Substituted Ethenyl Thiophenes - Naresh Kumar; Jagdeep Kumar; Prasanta Kumar Hota (Journal of Fluorescence, 2017)

Spatial and temporal variation in daily temperature indices in summer and winter seasons over India (1969–2012) - Naresh Kumar; A. K. Jaswal; M. Mohapatra; P. A. Kore (Theoretical and Applied Climatology, 2017)

Quantum chemical, ADMET and molecular docking studies of ferulic acid amide derivatives with a novel anticancer drug target - Naresh Kumar; Nidhi Goel; Tara Chand Yadav; Vikas Pruthi (Medicinal Chemistry Research, 2017)

Meteorological features associated with unprecedented precipitation over India during 1st week of March 2015 - Naresh Kumar; M Mohapatra; A K Jaswal (Journal of Earth System Science, 2017)

Evaluation of cellulose of Valoniopsis pachynema (Martens) Børgesen for its applications in paper making - Naresh D Sanandiya; Chandrakant Mukesh; Arun Kumar Das.; Kamalesh Prasad; A.K. Siddhanta (Journal of Applied Phycology, 2017)

Chemical characteristics and source apportionment of PM2.5 using PCA/APCS, UNMIX, and PMF at an urban site of Delhi, India - Srishti Jain; Sudhir Kumar Sharma; Nikki Choudhary; Renu Masiwal; Mohit Saxena; Ashima Sharma; Tuhin Kumar Mandal; Anshu Gupta; Naresh Chandra Gupta; Chhemendra Sharma (Environmental Science and Pollution Research, 2017)

Simulation of leaf blast infection in tropical rice agro-ecology under climate change scenario - K. Viswanath; P. Sinha; S. Naresh Kumar; Taru Sharma; Shalini Saxena; Shweta Panjwani; H. Pathak; Shalu Mishra Shukla (Climatic Change, 2017)

Cytogenetic investigation of Cyprinus carpio (Linnaeus, 1758) using giemsa, silver nitrate, CMA3 staining and fluorescence in situ hybridization - Ravindra Kumar; Vishwamitra Singh Baisvar; Basdeo Kushwaha; Gusheinzed Waikhom; Naresh Sahebrao Nagpure (The Nucleus, 2017)

Enhanced transportability of zero valent iron nanoparticles in aquifer sediments: surface modifications, reactivity, and particle traveling distances - Naresh Kumar; Jérôme Labille; Nathan Bossa; Mélanie Auffan; Pierre Doumenq; Jérôme Rose; Jean-Yves Bottero (Environmental Science and Pollution Research, 2017)

Malabsorption, Orocecal Transit Time and Small Intestinal Bacterial Overgrowth in Type 2 Diabetic Patients: A Connection - S. V. Rana; Aastha Malik; Sanjay K. Bhadada; Naresh Sachdeva; Rajesh Kumar Morya; Gaurav Sharma (Indian Journal of Clinical Biochemistry, 2017)

High day–night transition temperature alters nocturnal starch metabolism in rice (Oryza sativa L.) - Nitin Sharma; Archana Yadav; Sangeeta Khetarpal; Anjali Anand; Lekshmy Sathee; Ranjeet Ranjan Kumar; Bhupinder Singh; Naresh Kumar Soora; Suchitra Pushkar (Acta Physiologiae Plantarum, 2017)

A potato model intercomparison across varying climates and productivity levels - David H. Fleisher; Bruno Condori; Roberto Quiroz; Ashok Alva; Senthold Asseng; Carolina Barreda; Marco Bindi; Kenneth J. Boote; Roberto Ferrise; Angelinus C. Franke; Panamanna M. Govindakrishnan; Dieudonne Harahagazwe; et al. (Global Change Biology, 2017)
A potato crop multimodel assessment was conducted to quantify variation among models and evaluate responses to climate change. Nine modeling groups simulated agronomic and climatic responses at low‐input (Chinoli, Bolivia and Gisozi, Burundi)‐ and high‐input (Jyndevad, Denmark and Washington, United States) management sites. Two calibration stages were explored, partial (P1), where experimental dry matter data were not provided, and full (P2). The median model ensemble response outperformed any single model in terms of replicating observed yield across all locations. Uncertainty in simulated yield decreased from 38% to 20% between P1 and P2. Model uncertainty increased with interannual variability, and predictions for all agronomic variables were significantly different from one model to another ( P ET ), nitrogen uptake, and water use efficiency as compared to dry matter. A minimum of five partial, or three full, calibrated models was required for an ensemble approach to keep variability below that of common field variation. Model variation was not influenced by change in carbon dioxide (C), but increased as much as 41% and 23% for yield and ET , respectively, as temperature (T) or rainfall (W) moved away from historical levels. Increases in T accounted for the highest amount of uncertainty, suggesting that methods and parameters for T sensitivity represent a considerable unknown among models. Using median model ensemble values, yield increased on average 6% per 100‐ppm C, declined 4.6% per °C, and declined 2% for every 10% decrease in rainfall (for nonirrigated sites). Differences in predictions due to model representation of light utilization were significant ( P

One pot synthesis of silver nanocrystals using the seaweed Gracilaria edulis: biophysical characterization and potential against the filariasis vector Culex quinquefasciatus and the midge Chironomus circumdatus - Pari Madhiyazhagan; Kadarkarai Murugan; Arjunan Naresh Kumar; Thiyagarajan Nataraj; Jayapal Subramaniam; Balamurugan Chandramohan; Chellasamy Panneerselvam; Devakumar Dinesh; Udaiyan Suresh; Marcello Nicoletti; Mohamad Saleh Alsalhi; Sandhanasamy Devanesan; et al. (Journal of Applied Phycology, 2017)

Efficacy of rhizobial and phosphate-solubilizing bacteria and arbuscular mycorrhizal fungi to ameliorate shade response on six pulse crops - Ashok Shukla; Anil Kumar; Om Prakash Chaturvedi; Taru Nagori; Naresh Kumar; Ajit Gupta (Agroforestry Systems, 2017)

Sero-detection of Toxocara canis infection in human with T.canis recombinant arginine kinase, cathepsin L-1 and TES-26 antigens - Anju Varghese; Opinder K. Raina; Dinesh Chandra; Bijay R. Mirdha; Naresh H. Kelawala; Jayesh B. Solanki; Niranjan Kumar; Reghu Ravindran; Anandanarayanan Arun; Ajayta Rialch; Hniang Lalrinkima; Rohan N. Kelawala; et al. (Acta Parasitologica, 2017)
Three recombinant antigens

Physicochemical and Gel Properties of Myofibrillar Protein from Sin Croaker ( Johnius dussumieri ) Fish During Ice Storage - Naresh Kumar Mehta; Mithlesh K. Chouksey; Amjad K. Balange; Gayatri Tripathi; Binaya Bhusan Nayak (Journal of Aquatic Food Product Technology, 2017)

Integrated effect of population and weed management regimes on weed dynamics, performance, and productivity of basmati rice (Oryza sativa L.) - Roop Kishore; Ashish Dwivedi; Raghuvir Singh; R. K. Naresh; Vineet Kumar; Priyanka Bankoti; Dinesh Kumar Sharma; Nishant Yadav (Paddy and Water Environment, 2017)

Sucrose dependent mineral phosphate solubilization in Enterobacter asburiae PSI3 by heterologous overexpression of periplasmic invertases - Chanchal Kumar; Jitendra Wagh; G. Archana; G. Naresh Kumar (World Journal of Microbiology and Biotechnology, 2016)

Inoculation of genetically modified endophytic Herbaspirillum seropedicae Z67 endowed with gluconic and 2-ketogluconic acid secretion, confers beneficial effects on rice (Oriza sativa) plants - Jitendra Wagh; Kumar Chanchal; Shah Sonal; Bhandari Praveena; G. Archana; G. Naresh Kumar (Plant and Soil, 2016)

Ensifer meliloti overexpressing Escherichia coli phytase gene (appA) improves phosphorus (P) acquisition in maize plants - Vikas Sharma; Ajit Kumar; G. Archana; G. Naresh Kumar (The Science of Nature, 2016)

Cryopreservation of adult primate testes - Lavanya Pothana; Naresh Kumar Venna; Lalitha Devi; Anju Singh; Ipsita Chatterjee; Sandeep Goel (European Journal of Wildlife Research, 2016)

Antifungal and phytotoxic activity of essential oil from root of Senecio amplexicaulis Kunth. (Asteraceae) growing wild in high altitude-Himalayan region - Rajendra Singh; Vivek Ahluwalia; Pratap Singh; Naresh Kumar; Om Prakash Sati; Nitin Sati (Natural Product Research, 2016)

Crop establishment methods: foliar and basal nourishment of rice (Oryza sativa) cultivation affecting growth parameters, water saving, productivity and soil physical properties - R. K. Naresh; R. S. Rathore; S. S. Dhaliwal; R. B. Yadav; Dipender Kumar; S. P. Singh; Adil Nawaz; Narendra Kumar; Raj K. Gupta (Paddy and Water Environment, 2016)

Seismicity and stress inversion study in the Kangra–Chamba region of north-west Himalaya - Dilip Kumar Yadav; Devajit Hazarika; Naresh Kumar (Natural Hazards, 2016)

Ferulic acid amide derivatives as anticancer and antioxidant agents: synthesis, thermal, biological and computational studies - Naresh Kumar; Sandeep Kumar; Sheenu Abbat; Kumar Nikhil; Sham M. Sondhi; Prasad V. Bharatam; Partha Roy; Vikas Pruthi (Medicinal Chemistry Research, 2016)

Assessment of groundwater quality at a MSW landfill site using standard and AHP based water quality index: a case study from Ranchi, Jharkhand, India - Shubhrasekhar Chakraborty; R. Naresh Kumar (Environmental Monitoring and Assessment, 2016)

Antimicrobial activity of four cationic peptides immobilised to poly-hydroxyethylmethacrylate - Debarun Dutta; Naresh Kumar; Mark D. P. Willcox (Biofouling, 2016)

Analysis of unusual meteorological conditions that led to recent floods in Bhagirathi basin (Uttarakhand Himalayas) - Manohar Arora; Rakesh Kumar; R.D. Singh; Jatin Malhotra; Naresh Kumar (Hydrological Sciences Journal, 2016)

Historical temporal variation in precipitation over Western Himalayan Region: 1857-2006 - Naresh Kumar; Ashok Kumar Jaswal (Journal of Mountain Science, 2016)

Microbial and mineral evolution in zero valent iron-based permeable reactive barriers during long-term operations - Naresh Kumar; Romain Millot; Fabienne Battaglia-Brunet; Enoma Omoregie; Perrine Chaurand; Daniel Borschneck; Leen Bastiaens; Jérôme Rose (Environmental Science and Pollution Research, 2016)

Assessment of factors limiting algal growth in acidic pit lakes—a case study from Western Australia, Australia - R. Naresh Kumar; Cherie D. McCullough; Mark A. Lund; Santiago A. Larranaga (Environmental Science and Pollution Research, 2016)

Vulnerability of Indian mustard (Brassica juncea (L.) Czernj. Cosson) to climate variability and future adaptation strategies - Soora Naresh Kumar; Pramod Kumar Aggarwal; Kumar Uttam; Jain Surabhi; D. N. Swaroopa Rani; Nitin Chauhan; Rani Saxena (Mitigation and Adaptation Strategies for Global Change, 2016)

Potential Impacts of PCBs on Sediment Microbiomes in a Tropical Marine Environment - James Klaus; Vassiliki Kourafalou; Alan Piggot; Ad Reniers; HeeSook Kang; Naresh Kumar; Elsayed Zahran; Leonidas Bachas; Adolfo Fernandez; Piero Gardinali; Michal Toborek; Sylvia Daunert; et al. (Journal of Marine Science and Engineering, 2016)
Within the tropical marine study site of Guánica Bay, Puerto Rico, polychlorinated biphenyls (PCBs) are subjected to coastal and oceanic currents coupled with marine microbial and geochemical processes. To evaluate these processes a hydrodynamic model was developed to simulate the transport of PCBs within nearshore and offshore marine areas of Guánica Bay. Material transport and circulation information from the model were matched with measurements from samples collected from within the bay. These samples, consisting of both intertidal and submerged sediments, were analyzed for physical characteristics (organic carbon, grain size, and mineralogy), microbial characteristics (target bacteria levels and microbial community analyses), presence of PCBs, and PCB-degrading enzymes. Results show that the bay geometry and bathymetry limit the mixing of the extremely high levels of PCBs observed in the eastern portion of the bay. Bay bottom sediments showed the highest levels of PCBs and these sediments were characterized by high organic carbon content and finer grain size. Detectable levels of PCBs were also observed within sediments found along the shore. Microbes from the bay bottom sediments showed a greater relative abundance of microbes from the Chloroflexi, phylum with close phylogenetic associations with known anaerobic PCB-degrading organisms. Based on quantitative PCR measurement of the biphenyl dioxygenase gene, the intertidal sediments showed the greatest potential for aerobic PCB degradation. These results elucidate particular mechanisms of PCB’s fate and transport in coastal, tropical marine environments.

Environmental PCBs in Guánica Bay, Puerto Rico: implications for community health - Naresh Kumar; Daisy Ramirez-Ortiz; Helena M. Solo-Gabriele; Joseph B. Treaster; Olveen Carrasquillo; Michal Toborek; Sapna Deo; Jim Klaus; Leonidas G. Bachas; David Whitall; Sylvia Daunert; Jose Szapocznik (Environmental Science and Pollution Research, 2016)

Inhibition of cyclin-dependent kinase CDK1 by oxindolimine ligands and corresponding copper and zinc complexes - Rodrigo Bernardi Miguel; Philippe Alexandre Divina Petersen; Fernando A. Gonzales-Zubiate; Carla Columbano Oliveira; Naresh Kumar; Rafael Rodrigues do Nascimento; Helena Maria Petrilli; Ana Maria da Costa Ferreira (JBIC Journal of Biological Inorganic Chemistry, 2015)

Buffalo (Bubalus bubalis) term amniotic-membrane-derived cells exhibited mesenchymal stem cells characteristics in vitro - Kaushalya Ghosh; Rajesh Kumar; Jarnail Singh; S. K. Gahlawat; Dharmendra Kumar; Naresh Lalaji Selokar; S. P. Yadav; B. R. Gulati; P. S. Yadav (In Vitro Cellular & Developmental Biology - Animal, 2015)

Protection Against 1,2-Di-methylhydrazine-Induced Systemic Oxidative Stress and Altered Brain Neurotransmitter Status by Probiotic Escherichia coli CFR 16 Secreting Pyrroloquinoline Quinone - Sumeet Pandey; Ashish Singh; Nirja Chaudhari; Laxmipriya P. Nampoothiri; G. Naresh Kumar (Current Microbiology, 2015)

Cotton leaf curl Burewala virus with intact or mutant transcriptional activator proteins: complexity of cotton leaf curl disease - Jitendra Kumar; Samatha Gunapati; Anshu Alok; Adarsh Lalit; Rekha Gadre; Naresh C. Sharma; Joy K. Roy; Sudhir P. Singh (Archives of Virology, 2015)

Erratum to: Current status of tissue culture and genetic transformation research in cotton (Gossypium spp.) - Vijaya Naresh Juturu; Gopala Krishna Mekala; Giridara Kumar Surabhi; P. B. Kirti (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Effects of alumina nanoparticles in waste chicken fat biodiesel on the operating characteristics of a compression ignition engine - Naresh Kumar Gurusala; V Arul Mozhi Selvan (Clean Technologies and Environmental Policy, 2015)

Buffalo Embryonic, Fetal and Adult Stem Cells: Progress and Challenges - Dharmendra Kumar; T. Anand; Selokar Naresh Lalaji; P. S. Yadav; Inderjeet Singh (Agricultural Research, 2015)

Multimodel ensembles of wheat growth: many models are better than one - Pierre Martre; Daniel Wallach; Senthold Asseng; Frank Ewert; James W. Jones; Reimund P. Rötter; Kenneth J. Boote; Alex C. Ruane; Peter J. Thorburn; Davide Cammarano; Jerry L. Hatfield; Cynthia Rosenzweig; et al. (Global Change Biology, 2015)
Crop models of crop growth are increasingly used to quantify the impact of global changes due to climate or crop management. Therefore, accuracy of simulation results is a major concern. Studies with ensembles of crop models can give valuable information about model accuracy and uncertainty, but such studies are difficult to organize and have only recently begun. We report on the largest ensemble study to date, of 27 wheat models tested in four contrasting locations for their accuracy in simulating multiple crop growth and yield variables. The relative error averaged over models was 24–38% for the different end‐of‐season variables including grain yield ( GY ) and grain protein concentration ( GPC ). There was little relation between error of a model for GY or GPC and error for in‐season variables. Thus, most models did not arrive at accurate simulations of GY and GPC by accurately simulating preceding growth dynamics. Ensemble simulations, taking either the mean (e‐mean) or median (e‐median) of simulated values, gave better estimates than any individual model when all variables were considered. Compared to individual models, e‐median ranked first in simulating measured GY and third in GPC . The error of e‐mean and e‐median declined with an increasing number of ensemble members, with little decrease beyond 10 models. We conclude that multimodel ensembles can be used to create new estimators with improved accuracy and consistency in simulating growth dynamics. We argue that these results are applicable to other crop species, and hypothesize that they apply more generally to ecological system models.

Parathyroid Hormone (PTH) Assays and Applications to Bone Disease: Overview on Methodology - Ashutosh Kumar Arya; Naresh Sachdeva (Exposure and Health, 2015)

Isolation, Culture, In-Vitro Differentiation and Characterization of Canine Adult Mesenchymal Stem Cells - Sarabjot Singh; Dipak Deka; Raghunath Mulinti; Naresh Kumar Sood; Ravi Kant Agrawal; Ramneek Verma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Seasonal variation in the deformation rate in NW Himalayan region - D. D. Khandelwal; Vineet Gahalaut; Naresh Kumar; Bhaskar Kundu; Rajeev Kumar Yadav (Natural Hazards, 2014)

Overexpression of citrate operon in Herbaspirillum seropedicae Z67 enhances organic acid secretion, mineral phosphate solubilization and growth promotion of Oryza sativa - Jitendra Wagh; Praveena Bhandari; Sonal Shah; G. Archana; G. Naresh Kumar (Plant and Soil, 2014)

Anti-asthmatic activity of azepino [2, 1-b] quinazolones, synthetic analogues of vasicine, an alkaloid from Adhatoda vasica - Sheikh Rayees; Naresh Kumar Satti; Rukmankesh Mehra; Amit Nargotra; Shafaq Rasool; Anjna Sharma; Promod Kumar Sahu; Rajnikant; Vivek K. Gupta; Kunal Nepali; Gurdarshan Singh (Medicinal Chemistry Research, 2014)

Evaluation of 4-bromophenol biodegradation in mixed pollutants system by Arthrobacter chlorophenolicus A6 in an upflow packed bed reactor - Naresh Kumar Sahoo; Kannan Pakshirajan; Pranab Kumar Ghosh (Biodegradation, 2014)

Megha-Tropiques: mission planning, analysis, and operations - P. Vijayasree; Naresh Kumar; Ritu Karidhal; K. Harendranath; V. Kesava Raju; S.K. Shivakumar (International Journal of Remote Sensing, 2014)

How do various maize crop models vary in their responses to climate change factors? - Simona Bassu; Nadine Brisson; Jean‐Louis Durand; Kenneth Boote; Jon Lizaso; James W. Jones; Cynthia Rosenzweig; Alex C. Ruane; Myriam Adam; Christian Baron; Bruno Basso; Christian Biernath; et al. (Global Change Biology, 2014)
Potential consequences of climate change on crop production can be studied using mechanistic crop simulation models. While a broad variety of maize simulation models exist, it is not known whether different models diverge on grain yield responses to changes in climatic factors, or whether they agree in their general trends related to phenology, growth, and yield. With the goal of analyzing the sensitivity of simulated yields to changes in temperature and atmospheric carbon dioxide concentrations [ CO 2 ], we present the largest maize crop model intercomparison to date, including 23 different models. These models were evaluated for four locations representing a wide range of maize production conditions in the world: Lusignan (France), Ames ( USA ), Rio Verde (Brazil) and Morogoro (Tanzania). While individual models differed considerably in absolute yield simulation at the four sites, an ensemble of a minimum number of models was able to simulate absolute yields accurately at the four sites even with low data for calibration, thus suggesting that using an ensemble of models has merit. Temperature increase had strong negative influence on modeled yield response of roughly −0.5 Mg ha −1 per °C. Doubling [ CO 2 ] from 360 to 720 μmol mol −1 increased grain yield by 7.5% on average across models and the sites. That would therefore make temperature the main factor altering maize yields at the end of this century. Furthermore, there was a large uncertainty in the yield response to [ CO 2 ] among models. Model responses to temperature and [ CO 2 ] did not differ whether models were simulated with low calibration information or, simulated with high level of calibration information.

Biodegradation of 4-bromophenol by Arthrobacter chlorophenolicus A6 in batch shake flasks and in a continuously operated packed bed reactor - Naresh Kumar Sahoo; Kannan Pakshirajan; Pranab Kumar Ghosh (Biodegradation, 2014)

Characterization of fowl adenoviruses associated with hydropericardium syndrome and inclusion body hepatitis in broiler chickens - Dinesh Mittal; Naresh Jindal; Ashok Kumar Tiwari; Raj Singh Khokhar (VirusDisease, 2014)

Estimation of Q p and Q s of Kinnaur Himalaya - Naresh Kumar; Shonkholen Mate; Sagarika Mukhopadhyay (Journal of Seismology, 2014)

Impact of South China Sea Cold Surges and Typhoon Peipah on Initiating Cyclone Sidr in the Bay of Bengal - Naresh Krishna Vissa; A. N. V. Satyanarayana; B. Prasad Kumar (Pure and Applied Geophysics, 2013)

Stress drop and its relation to tectonic and structural elements for the meizoseismal region of great 1905 Kangra earthquake of the NW Himalaya - Naresh Kumar; Dilip K. Yadav; S. K. Mondal; P. N. S. Roy (Natural Hazards, 2013)

Upper and Lower Concentration Thresholds for Bulk Organic Substrates in Bioremediation of Acid Mine Drainage - R. Naresh Kumar; Cherie D. McCullough; Mark A. Lund (Mine Water and the Environment, 2013)

Response of upper ocean and impact of barrier layer on Sidr cyclone induced sea surface cooling - Naresh Krishna Vissa; A. N. V. Satyanarayana; B. Prasad Kumar (Ocean Science Journal, 2013)

Decline in horizontal surface visibility over India (1961–2008) and its association with meteorological variables - Ashok K. Jaswal; Naresh Kumar; Anup K. Prasad; Menas Kafatos (Natural Hazards, 2013)

Intensity of tropical cyclones during pre- and post-monsoon seasons in relation to accumulated tropical cyclone heat potential over Bay of Bengal - Naresh Krishna Vissa; A. N. V. Satyanarayana; B. Prasad Kumar (Natural Hazards, 2013)

Erratum to: Synthesis and biologic activities of some novel heterocyclic chalcone derivatives - Punita Sharma; Suresh Kumar; Furqan Ali; Sumati Anthal; Vivek K. Gupta; Inshad A. Khan; Surjeet Singh; Payare L. Sangwan; Krishan A. Suri; Bishan D. Gupta; Devinder K. Gupta; Prabhu Dutt; et al. (Medicinal Chemistry Research, 2013)

2-Ketogluconic Acid Secretion by Incorporation of Pseudomonas putida KT 2440 Gluconate Dehydrogenase (gad) Operon in Enterobacter asburiae PSI3 Improves Mineral Phosphate Solubilization - Chanchal Kumar; Kavita Yadav; G. Archana; G. Naresh Kumar (Current Microbiology, 2013)

Synthesis and biologic activities of some novel heterocyclic chalcone derivatives - Punita Sharma; Suresh Kumar; Furquan Ali; Sumati Anthal; Vivek K. Gupta; Inshad A. Khan; Surjeet Singh; Payare L. Sangwan; Krishan A. Suri; Bishan D. Gupta; Devinder K. Gupta; Prabhu Dutt; et al. (Medicinal Chemistry Research, 2013)

Earthquake precursory research in western Himalaya based on the multi-parametric geophysical observatory data - Naresh Kumar; Gautam Rawat; Vinay M. Choubey; Devajit Hazarika (Acta Geophysica, 2013)

Crustal thickness and Poisson’s ratio variations across the northwest Himalaya and eastern Ladakh - Devajit Hazarika; Naresh Kumar; Dilip Kumar Yadav (Acta Geophysica, 2013)

Effect of Different Growing Environments on Population Dynamics of Sucking Pests in Relation to Various Spectral Indices in Cotton - Naresh Kumar; Ram Niwas; M. L. Khichar; R. K. Saini; Barun Biswas (Journal of the Indian Society of Remote Sensing, 2013)

Insights into the P–T evolution path of Tso Morari eclogites of the north-western Himalayas: Constraints on the geodynamic evolution of the region - PREETI SINGH; ASHIMA SAIKIA; NARESH CHANDRA Pant; PRAMOD KUMAR VERMA (Journal of Earth System Science, 2013)

Spatiotemporal modeling of irregularly spaced aerosol optical depth data - Jacob J. Oleson; Naresh Kumar; Brian J. Smith (Environmental and Ecological Statistics, 2013)

An assessment of regional vulnerability of rice to climate change in India - Naresh Kumar Soora; P. K. Aggarwal; Rani Saxena; Swaroopa Rani; Surabhi Jain; Nitin Chauhan (Climatic Change, 2013)

A new betasatellite associated with cotton leaf curl Burewala virus infecting tomato in India: influence on symptoms and viral accumulation - Jitendra Kumar; Samatha Gunapati; Sudhir P. Singh; Abhinav Kumar; Adarsh Lalit; Naresh C. Sharma; Rekha Puranik; Rakesh Tuli (Archives of Virology, 2013)

Selective sensing of mercury(II) using PVC-based membranes incorporating recently synthesized 1,3-alternate thiacalix[4]crown ionophore - Rakesh Kumar Mahajan; Ajar Kamal; Naresh Kumar; Vandana Bhalla; Manoj Kumar (Environmental Science and Pollution Research, 2013)

Repression of oxalic acid-mediated mineral phosphate solubilization in rhizospheric isolates of Klebsiella pneumoniae by succinate - Mahendrapal Singh Rajput; G. Naresh Kumar; Shalini Rajkumar (Archives of Microbiology, 2013)

Development of EST-SSR markers and their utility in revealing cryptic diversity in safflower (Carthamus tinctorius L.) - Kalinati Narasimhan Yamini; Kamtam Ramesh; Vasupalli Naresh; Passoupathy Rajendrakumar; Kammili Anjani; Viswanathaswamy Dinesh Kumar (Journal of Plant Biochemistry and Biotechnology, 2013)

Construction of intersubspecific molecular genetic map of lentil based on ISSR, RAPD and SSR markers - MAMTA GUPTA; BHAWNA VERMA; NARESH KUMAR; RAKESH K. CHAHOTA; RAJEEV RATHOUR; SHYAM K. SHARMA; SABHYATA BHATIA; TILAK R. SHARMA (Journal of Genetics, 2012)

Trend and spatial distribution of rainfall & rainy days over Andaman & Nicobar Islands - Naresh Kumar; B. P. Yadav; Ajit Tyagi; A. K. Jaswal (Natural Hazards, 2012)

Spore germination based assay for monitoring antibiotic residues in milk at dairy farm - Naresh Kumar; Hirikyathanahalli Vishweswaraiah Raghu; Abhishek Kumar; Lopamudra Haldar; Alia Khan; Sharmila Rane; Ravinder Kumar Malik (World Journal of Microbiology and Biotechnology, 2012)

Antitussive effects of azepino[2,1-b]quinazolones - Kunal Nepali; Mukunda S. Bande; Sameer Sapra; Atul Garg; Sunil Kumar; Punita Sharma; Rohit Goyal; Naresh Kumar Satti; Om Parkash Suri; Kanaya Lal Dhar (Medicinal Chemistry Research, 2012)

Diversity of 21 taro (Colocasia esculenta (L.) Schott) accessions of Andaman Islands - Shrawan Singh; D. R. Singh; F. Faseela; Naresh Kumar; V. Damodaran; R. C. Srivastava (Genetic Resources and Crop Evolution, 2012)

Anti-arthritic activity of agnuside mediated through the down-regulation of inflammatory mediators and cytokines - Anjali Pandey; Sarang Bani; Naresh Kumar Satti; Bishan Dutt Gupta; Krishan Avtar Suri (Inflammation Research, 2012)

Sourcing Organic Materials for Pit Lake Bioremediation in Remote Mining Regions - R. Naresh Kumar; Cherie D. McCullough; Mark A. Lund; Michelle Newport (Mine Water and the Environment, 2011)

Determination of gene action for some biometrical traits in Lens culinaris Medik. under mid-hill conditions of northwestern Himalayas - NARESH KUMAR; B. C. SOOD; T. R. SHARMA; R. K. CHAHOTA; SALEJ SOOD (Journal of Genetics, 2011)

The cellulose contents of Indian seaweeds - A. K. Siddhanta; Mahesh U. Chhatbar; Gaurav K. Mehta; Naresh D. Sanandiya; Sanjay Kumar; Mihir D. Oza; Kamalesh Prasad; Ramavatar Meena (Journal of Applied Phycology, 2011)

A new hybrid spectral similarity measure for discrimination among Vigna species - M. Naresh Kumar; M. V. R. Seshasai; K. S. Vara Prasad; V. Kamala; K. V. Ramana; R. S. Dwivedi; P. S. Roy (International Journal of Remote Sensing, 2011)

Use of plant products and copepods for control of the dengue vector, Aedes aegypti - K. Murugan; Jiang-Shiou Hwang; K. Kovendan; K. Prasanna Kumar; C. Vasugi; A. Naresh Kumar (Hydrobiologia, 2011)

Cytogenetic characterization of an endemic mahseer, Tor mosal mahanadicus (David, 1953; Teleostei : Cyprinidae) - Indra Mani; Ravindra Kumar; Basdeo Kushwaha; Mamta Singh; Naresh S. Nagpure; Pramod K. Srivastava; Wazir S. Lakra (The Nucleus, 2010)

Characterisation and in vitro activities of surface attached dihydropyrrol-2-ones against Gram-negative and Gram-positive bacteria - Kitty K.K. Ho; Nerida Cole; Renxun Chen; Mark D.P. Willcox; Scott A. Rice; Naresh Kumar (Biofouling, 2010)

Estimates of source parameters of M4.9 Kharsali earthquake using waveform modelling - Ajay Paul; Naresh Kumar (Journal of Earth System Science, 2010)

Plasma pharmacokinetics and milk levels of ceftriaxone following single intravenous administration in healthy and endometritic cows - Sudershan Kumar; Anil K. Srivastava; V. K. Dumka; Naresh Kumar; Rajinder K. Raina (Veterinary Research Communications, 2010)

Simulating impacts, potential adaptation and vulnerability of maize to climate change in India - Kattarkandi Byjesh; Soora Naresh Kumar; Pramod Kumar Aggarwal (Mitigation and Adaptation Strategies for Global Change, 2010)

EST-SSR marker-based assay for the genetic purity assessment of safflower hybrids - V. Naresh; K. N. Yamini; P. Rajendrakumar; V. Dinesh Kumar (Euphytica, 2009)

Evaluation of Mimosa pudica Seed Mucilage as Sustained-Release Excipient - Kuldeep Singh; Ashok Kumar; Naresh Langyan; Munish Ahuja (AAPS PharmSciTech, 2009)

Synthesis, characterization and in vitro activity of a surface-attached antimicrobial cationic peptide - Renxun Chen; Nerida Cole; Mark D.P. Willcox; Josephine Park; Riaz Rasul; Elizabeth Carter; Naresh Kumar (Biofouling, 2009)

Amelioration of phytotoxic effects of Cd on mung bean seedlings by gluconic acid secreting rhizobacterium Enterobacter asburiae PSI3 and implication of role of organic acid - B. Kavita; Sapna Shukla; G. Naresh Kumar; G. Archana (World Journal of Microbiology and Biotechnology, 2008)

Variation in the Nature of Organic Acid Secretion and Mineral Phosphate Solubilization by Citrobacter sp. DHRSS in the Presence of Different Sugars - Divya K. Patel; G. Archana; G. Naresh Kumar (Current Microbiology, 2008)

Tomographic approach for gas hydrate investigation in Kerala-Konkan region, India - Naresh Kumar Thakur; Pasupuleti Prasada Rao; N. Vishwanath; Sanjeev Rajput; Bhaskarabhatla Ashalatha (Marine Geophysical Research, 2007)

Genetic variability and association studies in pod and seed traits of Pongamia pinnata (L.) Pierre in Haryana, India - Naresh Kaushik; Sushil Kumar; Krishan Kumar; R. S. Beniwal; N. Kaushik; S. Roy (Genetic Resources and Crop Evolution, 2007)

Biosorption of manganese by Aspergillus niger and Saccharomyces cerevisiae - K. Parvathi; R. Naresh Kumar; R. Nagendran (World Journal of Microbiology and Biotechnology, 2007)

Cadmium Level in Blood and Milk from Animals Reared Around Different Polluting Sources in India - R. C. Patra; D. Swarup; R. Naresh; P. Kumar; P. Shekhar; R. Ranjan (Bulletin of Environmental Contamination and Toxicology, 2005)

Restoration of impaired p38 activation by insulin in insulin resistant skeletal muscle cells treated with thiazolidinediones - Naresh Kumar; Chinmoy S. Dey (Molecular and Cellular Biochemistry, 2004)

Effect of flowering on juice quality and fibre content in sugarcane - P. N. Gururaja Rao; K. Naresh Kumar (Sugar Tech, 2003)

Role of soil microorganisms in improving P nutrition of plants - P. Gyaneshwar; G. Naresh Kumar; L. J. Parekh; P. S. Poole (Plant and Soil, 2002)

A novel and sensitive method for the quantification of N ‐3‐oxoacyl homoserine lactones using gas chromatography–mass spectrometry: application to a model bacterial biofilm - Timothy S. Charlton; Rocky De Nys; Andrew Netting; Naresh Kumar; Morten Hentzer; Michael Givskov; Staffan Kjelleberg (Environmental Microbiology, 2000)
A method is reported for the quantification of 3‐oxoacyl homoserine lactones (3‐oxo AHLs), a major class of quorum‐sensing signals found in Gram‐negative bacteria. It is based on the conversion of 3‐oxo AHLs to their pentafluorobenzyloxime derivatives followed by gas chromatography–mass spectrometry (electron capture–negative ion). The method used [ 13 C 16 ]‐ N ‐3‐oxo‐dodecanoyl homoserine lactone ([ 13 C 16 ]‐OdDHL) as the internal standard, and its validity was tested by spiking the supernatant and cell fractions with three levels of 3‐oxo AHLs, i.e. 1, 10 and 100 ng per sample. These showed the method to be both sensitive (S/N ratio > 10:1 for 1 ng) and accurate. The assay was applied to the biofilm and effluent of a green fluorescent protein (GFP)‐expressing strain of Pseudomonas aeruginosa (6294) culture grown in flow cells. Biofilm volume was determined for three replicate flow cells by confocal scanning laser microscopy. OdDHL was detected in the biofilm at 632 ± 381 µM and the effluent at 14 ± 3 nM. The biofilm concentration is the highest level so far reported for an AHL in a wild‐type bacterial system. The next most abundant 3‐oxo AHL in the biofilm and effluent was N ‐3‐oxo‐tetradecanoyl homoserine lactone (OtDHL) at 40 ± 15 µM and 1.5 ± 0.7 nM respectively. OtDHL is unreported for P. aeruginosa and has an activity equivalent to OdDHL in a lasR bioassay. Two other 3‐oxo AHLs were detected at lower concentrations: N ‐3‐oxo‐decanoyl homoserine lactone (ODHL) in the biofilm (3 ± 2 µM) and effluent (1 ± 0.1 nM); and N ‐3‐oxo‐octanoyl homoserine lactone (OOHL) in the effluent (0.1 ± 0.1 nM).

Effect of buffering on the phosphate-solubilizing ability of microorganisms - P. Gyaneshwar; G. Naresh Kumar; L.J. Parekh (World Journal of Microbiology and Biotechnology, 1998)

Rabies in a camel—A case report - Ashok Kumar; Naresh Jindal (Tropical Animal Health and Production, 1997)